Spin-on compositions comprising an inorganic oxide component and an alkynyloxy-substituted spin-on carbon component useful as hardmasks and fill materials with improved shelf life - Patents.com

A spin-on composition of metal compounds and alkynyloxy-functionalized carbon polymers addresses the instability and deposition challenges of conventional metal oxides, providing stable high-K films for semiconductor applications with improved shelf life and void filling capabilities.

JP7610518B2Active Publication Date: 2025-01-08MERCK PATENT GMBH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021549215
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-02-22
Filing Date
2020-02-20
Publication Date
2025-01-08
Estimated Expiration
2040-02-20

AI Technical Summary

Technical Problem

Conventional metal oxide films used in semiconductor manufacturing are unstable to atmospheric moisture, leading to shelf-life issues and performance problems, and require expensive chemical vapor deposition (CVD) for deposition, which lacks planarization on patterned substrates with deep vias or trenches.

Method used

A composition comprising a metal compound with specific organic moieties and a spin-on carbon polymer functionalized with alkynyloxy groups, which can be spin-coated and patterned without CVD, providing stable high-K metal oxides for void filling and serving as hard masks.

Benefits of technology

The composition offers air-stable, thermally stable high-K metal oxides with improved shelf life and minimal void formation, suitable for filling patterned substrates and functioning as effective hard masks in semiconductor processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610518000001
    Figure 0007610518000001
  • Figure 0007610518000002
    Figure 0007610518000002
  • Figure 0007610518000003
    Figure 0007610518000003
Patent Text Reader

Abstract

The present invention relates to a composition comprising components a), b), and d), wherein component a) is a metal compound having structure (I); component b) is a spin-on high carbon polymer having a polymer backbone comprising a monocyclic aromatic hydrocarbon, a fused ring cyclic hydrocarbon moiety, or a mixture thereof, the weight percent carbon being from about 81 weight percent to about 94 weight percent, and the spin-on high carbon polymer being at least about 5 weight percent soluble in a spin-casting solvent, wherein at least one of the monocyclic aromatic hydrocarbon or the fused ring cyclic hydrocarbon moiety present in the spin-on high carbon polymer is functionalized with at least one alkynyloxy moiety of structure (VIII); and component d) is a spin-casting solvent. The present invention further relates to the use of this composition in methods for manufacturing electronic devices through the formation of patterned films of high-K materials composed of metal oxides on semiconductor substrates, or through the formation of patterned metal oxide composition layers covering semiconductor substrates that can be used to selectively etch the semiconductor substrates using fluorine plasma. TIFF2022521531000107.tif37170
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to compositions useful as air-stable precursors to high-K metal oxides with good shelf life, comprising soluble multi-ligand-substituted metal compounds and alkynyloxy-substituted spin-on carbon components. These precursors exhibit good void-filling capabilities for trench or via microlithographic features, and after fabrication of these filled lithographic features, substrates containing patterned high-K metal oxides can be produced without the use of chemical vapor deposition (CVD). These materials can also be used as hardmask materials. [Background technology]

[0002] Metal oxide films are useful in a variety of applications in the semiconductor industry, such as hard masks for lithography, underlayers for antireflective coatings, and electro-optical devices.

[0003] As an example, photoresist compositions are used in microlithography processes for the production of miniaturized electronic components, such as in the fabrication of computer chips and integrated circuits. Typically, a thin coating of a photoresist composition is applied to a substrate, such as a silicon wafer used in the fabrication of integrated circuits. The coated substrate is then baked to remove a desired amount of solvent from the photoresist. The photoresist film is then imagewise exposed to actinic radiation, such as visible light, ultraviolet light, extreme ultraviolet light, electron beam, particle beam, and X-ray radiation, and developed to form a pattern. The radiation causes a chemical change in the exposed areas of the photoresist. The exposed coating is then treated with a developer solution to dissolve and remove either the radiation-exposed or unexposed areas of the photoresist.

[0004] As semiconductor devices continue to shrink in size, new photoresists sensitive to shorter wavelength radiation and sophisticated multi-level systems are being used to overcome the problems associated with this shrinkage.

[0005] Absorbing coatings and underlayers in photolithography are often used to mitigate problems resulting from radiation reflecting off highly reflective substrates. Reflected radiation can lead to thin-film interference effects and reflective notching. Thin-film interference or standing waves result in minute linewidth dimension variations caused by variations in total light intensity in the photoresist film when the photoresist thickness changes. Interference between reflected and incident exposure radiation can create standing wave effects that distort the through-thickness radiation uniformity. Reflective notching becomes severe when forming patterns on reflective substrates that contain topographical features that scatter light in the photoresist film, resulting in linewidth variations and, in extreme cases, areas where the desired dimensions are completely lost. Antireflective coating films coated under the photoresist and on top of the reflective substrate can significantly improve the lithographic performance of the photoresist. Typically, a bottom antireflective coating is applied to the substrate and cured, followed by a layer of photoresist. The photoresist is imagewise exposed and developed. The antireflective coating in the exposed areas is then typically dry etched using various etching gases, thus transferring the photoresist pattern into the substrate.

[0006] An underlayer containing a large amount of refractory elements can be used as a hard mask and an antireflective coating. Hard masks are useful when the overlying photoresist cannot provide sufficient resistance to the dry etching used to transfer an image into the underlying semiconductor substrate. In such circumstances, a material called a hard mask is used, which has a sufficiently high etch resistance to transfer any pattern formed on it into the underlying semiconductor substrate. This is possible because the organic photoresist is different from the underlying hard mask and can be applied with an etching gas mixture that allows the image in the photoresist to be transferred to the underlying hard mask. This patterned hard mask can then be used to transfer the image from the hard mask to the semiconductor substrate using appropriate etching conditions and gas mixtures, a task that photoresist alone cannot accomplish in a single etching process.

[0007] Multilayer antireflective layers and underlayers are being used in new lithography techniques. When photoresists do not provide sufficient dry etching resistance, underlayers and / or antireflective coatings for photoresists that act as hard masks and have high etching resistance during substrate etching are preferred. One approach has been to incorporate silicon, titanium, or other metal materials into layers beneath organic photoresist layers. Additionally, other high-carbon content antireflective or mask layers can be placed beneath metal-containing antireflective layers, for example, a high-carbon film / hardmask film / photoresist trilayer, to enhance the lithographic performance of the imaging process. Conventional hardmasks can be applied by chemical vapor deposition methods such as sputtering. However, due to the relative simplicity of spin-coating compared to the conventional approaches described above, the development of new spin-on hardmasks or antireflective coatings containing high concentrations of metal materials in the film is highly desirable.

[0008] Underlayer compositions for semiconductor applications containing metal oxides have been shown to provide dry etch resistance and antireflective properties. However, conventional soluble metal compounds for forming metal oxide films, such as metal alkoxides, have been found to be highly unstable to atmospheric moisture, resulting in various problems, including shelf-life stability, coating issues, and performance shortcomings. Metal oxides have solubility issues in typically used solvents found in the semiconductor industry. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] US3474054B [Patent Document 2] US4200729B [Patent Document 3] US4251665B [Patent Document 4] US5187019B Summary of the Invention [Problem to be solved by the invention]

[0010] For decades, silicon dioxide (SiO2) has been used as the gate oxide material. However, as transistors are scaled down to improve device performance, the thickness of the silicon dioxide gate dielectric is becoming thinner and thinner in order to increase gate capacitance and therefore drive current. Equation 1 shows this relationship between capacitance and gate oxide, where a MOSFET (metal-oxide-semiconductor field-effect resistor) is modeled as a simple parallel-plate capacitor, ignoring quantum mechanical and depletion effects from the Si substrate and gate. In Equation 1, A is the area of ​​the capacitor; κ is the relative permittivity of the material (3.9 for silicon dioxide); ε is the permittivity of free space; and t is the thickness of the capacitor oxide insulator.

[0011]

number

[0012] Upon processing, these filled lithographic features result in substrates bearing patterned high-K metal oxides derived from the compositions of the present invention. In addition to their use as high-K materials, these novel compositions are useful as hard masks, and in this capacity, they can also be used to form patterned hard masks on semiconductor substrates (e.g., silicon, germanium, etc.) to enable substrate patterning via plasma etching processes. These hard mask patterns can be generated by patterning a coating of the novel composition onto an unpatterned substrate using conventional photoresist patterning methods. Alternatively, the pattern can result from filling topography already present in the semiconductor substrate or in an overlying patterned resist or patterned spin-on carbon layer. In any hard mask application, after pattern transfer into the substrate is complete, the remaining hard mask pattern can be stripped in a chemical solution. [Means for solving the problem]

[0013] The present invention relates to a composition comprising components a), b) and d), and optionally component c), wherein component a) is a metal compound having the following structure (I):

[0014] [ka] In structure (I), M is a metal having a valence of 4; n is an integer from 1 to 20, and R1, R2, R3, and R4 are each a moiety independently selected from the group consisting of 1), 2), and 3).

[0015] In structure (I), moiety 1) is a first organic moiety having structure (II): In structure (II), R5 is a C2-C 10 Alkylene, C3-C 12 Branched alkylene, C5-C 12 Cycloalkylene, C2-C containing C=C double bond 10 Alkylene, C3-C containing C=C double bond12 Branched alkylene and C5-C including C=C double bonds 12 and R6 is hydrogen or alkyloxycarbonyl having structure (III): In structure (III), R7 is C1-C8 alkyl.

[0016] [ka] In structure (I), moiety 2) is a silicon-containing organic moiety having at least two carbons and having structure (IV): In structure (IV), R8 and R9 are C1-C8 alkyl, C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl; R 10 is C1-C8 alkyl, C6-C 16 is selected from the group consisting of aryl, and hydroxy, and siloxanes having structure (V): In structure (V), R 11 is hydrogen, C1-C8 alkyl, C1-C8 alkyl substituted with hydroxyl, C6-C 16 aryl, and a silyl moiety having the structure (IVa); R 12 and R 13 are C1-C8 alkyl and C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl; and p represents the number of repeating units in the siloxane portion (V). In structure (IVa), R 8a and R 9a are C1-C8 alkyl and C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl; R 10a is C1 to C8 alkyl and C6 to C16 aryl.

[0017] [ka] In structure (I), moiety 3) is C2-C8 alkyl, C2-C8 alkylcarboxyl, C6-C 20 The second organic moiety is selected from the group consisting of aryl carboxyl, fluorenyl carboxyl, fluorinated C2-C8 alkyl carboxyl, C2-C8 alkyl sulfonyl, fluorinated C2-C8 alkyl sulfonyl, and mixtures thereof.

[0018] In structure (I), the moieties selected may be a mixture of the moieties described above in this structure.

[0019] In the above compositions according to the present invention, component b) is a spin-on high carbon polymer having a polymer backbone comprising a monocyclic aromatic hydrocarbon moiety, a fused ring cyclic hydrocarbon moiety, or a mixture thereof, a weight percent carbon of about 81 weight percent to about 94 weight percent, and soluble in a spin-casting solvent at least at about 5 weight percent, and at least one of the monocyclic aromatic hydrocarbon or fused ring cyclic hydrocarbon moieties in the spin-on high carbon polymer is functionalized with at least one alkynyloxy moiety of structure (VIII).

[0020] [ka] In structure (VIII),

[0021] [ka] represents the point of attachment of the alkynyloxy moiety to the monocyclic aromatic hydrocarbon or to the fused ring cyclic hydrocarbon moiety, and R a1is hydrogen, halogen, cyano, unsubstituted C1-C6 alkyl; C1-C6 alkyl substituted with at least one substituent selected from the group consisting of C1-C6 alkyl, halogen, and cyano; unsubstituted C3-C 20 Aromatic ring; or C3-C substituted with at least one substituent selected from the group consisting of C1-C6 alkyl, halogen, and cyano. 20 is an aromatic ring, and R a2 and R a3 are each independently selected from the group consisting of hydrogen, halogen, cyano, unsubstituted C1-C6 alkyl; C1-C6 alkyl substituted with at least one substituent selected from the group consisting of C1-C6 alkyl, halogen, and cyano; unsubstituted C3-C 20 Aromatic ring; or C3-C substituted with at least one substituent selected from the group consisting of C1-C6 alkyl, halogen, and cyano. 20 It is an aromatic ring.

[0022] Optional component c) in the composition according to the present invention above is a polyol additive having structure (VI), where X is C or N; r is at least 2; q is 0 to 2; provided that the sum of q and r is 4 when X is C, and the sum of q and r is 3 when X is N; R 14 is selected from the group consisting of hydrogen, C1-C8 alkyl, and C2-C8 hydroxyalkyl. When X is N, Y is C1-C8 alkylene. When X is C, Y is selected from the group consisting of a direct valence bond, C1-C8 alkylene, and a moiety having structure (VII), where in structure (VII), R 15 is a C2-C8 alkylene; s is 0-2; and t is 1-2.

[0023] [ka] Component d) in the composition according to the invention described above is a solvent.

[0024] The present invention also relates to the use of the compositions according to the present invention as precursors to high-K metal oxides. The present invention further relates to the use of the compositions according to the present invention to fill lithographic features on a substrate, resulting in a substrate comprising a patterned high-K metal oxide after processing.

[0025] Specifically, the present invention relates to using these novel air-stable compositions to coat patterned substrates, be they patterned photoresist, patterned spin-on carbon, or patterned semiconductors containing vias, trenches, holes, or other hollow topographical features, filling these voids with low void formation, and using these filled patterns in a process to form patterned metal oxides on the substrate. DETAILED DESCRIPTION OF THE INVENTION

[0026] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to restrict the invention as claimed. As used herein, unless specifically stated otherwise, the use of the singular includes the plural, the singular means "at least one," and the use of "or" means "and / or." Furthermore, the use of the term "comprises" and other verb forms, such as "comprises," is not limiting. Furthermore, the use of terms such as "element" or "component" includes both elements and components containing one unit and elements or components containing more than one unit, unless specifically stated otherwise. Unless otherwise indicated, the conjunction "and" as used herein is intended to be inclusive, and the conjunction "or" is not intended to be exclusive. For example, the phrase "or instead" is intended to be exclusive. As used herein, the conjunction "and" refers to any combination of the aforementioned elements, including the use of a single element.

[0027] The section headings used herein are for organizational purposes only and should not be construed as limiting the technical subject matter described. All references or portions thereof cited herein, including but not limited to patents, patent applications, papers, books, and treatises, are incorporated herein in their entirety for all purposes. In the event that the definition of a term in one or more of the references and similar materials cited herein conflicts with that herein, the definition herein shall control.

[0028] Unless otherwise indicated, the conjunction "and" as used herein is intended to be inclusive and the conjunction "or" is not intended to be exclusive. For example, the phrase "or alternatively" is intended to be exclusive.

[0029] As used herein, the term "and / or" refers to any combination of the listed elements, including the use of any single element.

[0030] As used herein, the phrase "M is a metal having a valence of 4" includes metalloids having a valence of 4, such as silicon, germanium, and the like, unless otherwise specified.

[0031] As used herein, the term "alkyl" refers to all straight-chain or cyclic alkyl substituents, as well as their branched isomers. More specifically, unless otherwise specified herein, alkyl refers to hydrocarbon groups that can be linear, branched (e.g., methyl, ethyl, propyl, isopropyl, tert-butyl, and the like), cyclic (e.g., cyclohexyl, cyclopropyl, cyclopentyl, and the like), or polycyclic (e.g., norbornyl, adamantyl, and the like). These alkyl moieties may be substituted or unsubstituted as described below. The term alkyl refers to C1-C 20"alkyl" refers to a moiety having 1 to 5 carbon atoms. For structural reasons, linear alkyls are understood to begin at C1, while branched alkyls begin at C3, and polycyclic alkyls begin at C5. Furthermore, moieties derived from alkyls described below, such as substituted alkyls, are also understood to have the same carbon number ranges unless otherwise specified. When a different alkyl group length is specified, the above definition of alkyl remains valid in that it encompasses all types of alkyl moieties described above, and the structural considerations described above regarding the minimum carbon number of a given type of alkyl group still apply.

[0032] Alkyloxy (also known as alkoxy) refers to an alkyl group, as defined above, attached through an oxy (—O—) moiety (e.g., methoxy, ethoxy, propoxy, butoxy, 1,2-isopropoxy, cyclopentyloxy, cyclohexyloxy, and the like), which alkyloxy moieties may be substituted or unsubstituted as described below.

[0033] Here, alkyl and alkyloxy moieties having a range of possible carbon atoms starting from C1, such as, but not limited to, "C1-C 20 Alkyl" or "C1-C 20 When referring to "fluoroalkyl," this range includes C1 linear alkyl, alkyloxy, fluoroalkyl, and fluoroalkyloxy, but specifies only C3 branched alkyl, branched alkyloxy, cycloalkyl, cycloalkyloxy, branched fluoroalkyl, and cyclic fluoroalkyl.

[0034] The term "alkylene" as used herein refers to a hydrocarbon group that can be linear, branched, or cyclic and has two or more points of attachment (two points of attachment, e.g., methylene, ethylene, 1,2-isopropylene, 1,4-cyclohexylene, and the like; three points of attachment, e.g., 1,1,1-substituted methanes, 1,1,2-substituted ethanes, 1,2,4-substituted cyclohexanes, and the like). Again, the possible carbon ranges, e.g., C1-C, are used as non-limiting examples. 20 When specifying a group, the range includes linear alkylene starting from C1, but specifies only branched alkylene or cycloalkylene starting from C3. These alkylene moieties may be substituted or unsubstituted as described below. More specifically, as used herein, the term "linear alkylene" refers to a group having the general formula -CH2-(CH2) n The term "branched alkylene," as used herein, refers to an alkylene substituent having an alkyl substituent.

[0035] As used herein, the term "aryl" refers to any functional group or substituent derived from an aromatic ring, such as phenyl, naphthyl, thienyl, indolyl, etc. More specifically, the term aryl or aromatic group herein refers to such groups having from 6 to 24 carbon atoms, including phenyl, tolyl, xylyl, naphthyl, anthracyl, biphenyls, bis-phenyls, tris-phenyls, and the like. These aryl groups may be further substituted with any of the suitable substituents described above, such as alkyl, alkoxy, acyl, or aryl groups described above.

[0036] As used herein, the term halide refers to a halo substituent selected from the group consisting of F, Cl, Br, and I.

[0037] Unless otherwise stated herein, the term "substituted," when referring to aryl, alkyl, or alkyloxy, refers to one of these moieties that also includes one or more substituents selected from the group consisting of unsubstituted alkyl, substituted alkyl, unsubstituted aryl, alkyloxyaryl (alkyl-O-aryl-), dialkyloxyaryl ((alkyl-O-)2-aryl), haloaryl, alkyloxy, alkylaryl, haloalkyl, halide, hydroxyl, cyano, nitro, acetyl, and alkylcarbonyl.

[0038] The term "substituted," when referring to a moiety, means that, unless otherwise specified, the substituents are selected from any of the above substituents. Similarly, the term "unsubstituted" refers to the same moiety where there are no substituents other than hydrogen.

[0039] As used herein, the term "diketone" refers to any solvent that has two ketone groups; non-limiting examples are diacetyl, acetylacetone, and hexane-2,5-dione.

[0040] As used herein, the terms "composition" and "formulation" are interchangeable and synonymous.

[0041] As used herein, the terms "spin-on carbon layer" and "organic high carbon coating" are interchangeable and have the same meaning.

[0042] As used herein, unless otherwise specified, the term "patterned substrate" refers to: 1) a patterned semiconductor substrate; 2) a patterned photoresist covering the semiconductor substrate, or a semiconductor coated with an underlayer such as an antireflective coating; 3) a patterned organic high-carbon coating on a semiconductor substrate, where the original high-carbon material coating may be derived from a coated high-carbon polymer film; a coated spin-on carbon material; or a high-carbon content film deposited on a semiconductor substrate by other means, such as vapor deposition.

[0043] As used herein, the terms high-k material, high-k metal oxide, and high-k composed of metal oxide are interchangeable.

[0044] The present invention relates to a composition comprising components a), b) and d), and optionally component c).

[0045] Component a) is a metal compound having the structure (I).

[0046] [ka] In structure (I), M is a metal having a valence of 4; n is an integer from 1 to 20, and R1, R2, R3, and R4 are each a moiety independently selected from the group consisting of 1), 2), and 3).

[0047] In structure (I), moiety 1) is a first organic moiety having structure (II): In structure (II), R5 is a C2-C 10 Alkylene, C3-C 12 Branched alkylene, C5-C 12 Cycloalkylene, C2-C containing C=C double bond 10 Alkylene, C3-C containing C=C double bond 12 Branched alkylene and C5-C including C=C double bonds 12cycloalkylene, and R6 is hydrogen or alkyloxycarbonyl having the structure (III), wherein in structure (III), R7 is C1-C8 alkyl.

[0048] [ka] In structure (I), moiety 2) is a silicon-containing organic moiety having at least two carbons and having structure (IV): In structure (IV), R8 and R9 are C1-C8 alkyl, C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl; R 10 is C1-C8 alkyl, C6-C 16 is selected from the group consisting of aryl, and hydroxy, and siloxanes having structure (V): In structure (V), R 11 is hydrogen, C1-C8 alkyl, C1-C8 alkyl substituted with hydroxyl, C6-C 16 aryl, and a silyl moiety having the structure (IVa); R 12 and R 13 are C1-C8 alkyl and C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl; and p represents the number of repeating units in the siloxane portion (V). In structure (IVa), R 8a and R 9a are C1-C8 alkyl and C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl; R 10a is C1 to C8 alkyl and C6 to C 16 aryl.

[0049] [ka] In structure (I), moiety 3) is C2-C8 alkyl, C2-C8 alkylcarboxyl, C6-C 20 The second organic moiety is selected from the group consisting of aryl carboxyl, fluorenyl carboxyl, fluorinated C2-C8 alkyl carboxyl, C2-C8 alkyl sulfonyl, fluorinated C2-C8 alkyl sulfonyl, and mixtures thereof.

[0050] In structure (I), the moieties selected may be a mixture of the moieties described above in this structure.

[0051] Component b) is a spin-on high carbon polymer having a polymer backbone comprising a monocyclic aromatic hydrocarbon moiety, a fused ring cyclic hydrocarbon moiety, or a mixture thereof, a weight percent carbon of about 81 weight percent to about 94 weight percent, and at least about 5 weight percent soluble in a spin-casting solvent, and wherein the monocyclic aromatic hydrocarbon moiety or the fused ring cyclic hydrocarbon moiety in the spin-on high carbon polymer is functionalized with at least one alkynyloxy moiety of structure (VIII).

[0052] [ka] In structure (VIII),

[0053] [ka] represents the point of attachment of the alkynyloxy moiety to the monocyclic aromatic hydrocarbon or to the fused ring cyclic hydrocarbon moiety, and R a1 is hydrogen, halogen, cyano, unsubstituted C1-C6 alkyl; C1-C6 alkyl substituted with at least one substituent selected from the group consisting of C1-C6 alkyl, halogen, and cyano; unsubstituted C3-C 20Aromatic ring; or C3-C substituted with at least one substituent selected from the group consisting of C1-C6 alkyl, halogen, and cyano. 20 is an aromatic ring, and R a2 and R a3 are each independently selected from the group consisting of hydrogen, halogen, cyano, unsubstituted C1-C6 alkyl; C1-C6 alkyl substituted with at least one substituent selected from the group consisting of C1-C6 alkyl, halogen, and cyano; unsubstituted C3-C 20 Aromatic ring; or C3-C substituted with at least one substituent selected from the group consisting of C1-C6 alkyl, halogen, and cyano. 20 It is an aromatic ring.

[0054] Optional component c) in the composition according to the present invention above is a polyol additive having structure (VI), where X is C or N; r is at least 2; q is 0 to 2; provided that the sum of q and r is 4 when X is C, and the sum of q and r is 3 when X is N; R 14 is selected from the group consisting of hydrogen, C1-C8 alkyl, and C2-C8 hydroxyalkyl. When X is N, Y is C1-C8 alkylene. When X is C, Y is selected from the group consisting of a direct valence bond, C1-C8 alkylene, and a moiety having structure (VII). In structure (VII), R 15 is a C2-C8 alkylene; s is 0-2; and t is 1-2.

[0055] [ka] In the compositions according to the invention described above, component d) is a spin-casting solvent.

[0056] composition Component a), metal compound In one embodiment of the composition of the invention described above, in structure (I), M is selected from the group consisting of Zr, Ta, Hf, Ti, Sn, Si, Pb, Nb, Mo, Ge, and W. In another embodiment of this aspect of the composition of the invention, M is selected from the group consisting of Zr, Hf, Ti, Ta, Nb, and Sn. In yet another embodiment, M is selected from Zr, Hf, and Ti. In yet another embodiment, M is Zr. In yet another embodiment, M is Hf. In yet another embodiment, M is Ti.

[0057] In yet another embodiment, component a) is a mixture of two or more different metal compounds having structure (I).

[0058] In yet another embodiment, component a) is a mixture of two or more different metal compounds having structure (I) with different M's.

[0059] In another embodiment, component a) is a mixture of two or more different metal compounds having structure (I), wherein M is selected from the group consisting of Si, Zr, Ta, Hf, Ti, Sn, Si, Pb, Nb, Mo, Ge, and W, and further wherein at least one metal compound in the mixture does not have M equal to Si.

[0060] In another embodiment, component a) is a mixture of two different metal compounds having structure (I), wherein M of the first metal compound is Si and the second metal compound has an M selected from the group consisting of Zr, Ta, Hf, Ti, Sn, Si, Pb, Nb, Mo, Ge, and W, preferably Zr, Ta, Hf, Ti, Sn, Pb, Nb, Mo, Ge, and W. In yet another aspect of this embodiment, the second metal compound has an M equal to Zr. In another aspect of this embodiment, the second metal compound has an M equal to Hf. In yet another aspect of this embodiment, the second metal compound has an M equal to Ti.

[0061] In another embodiment of the composition of the present invention, in structure (I), at least one of the moieties for R1, R2, R3, and R4 is selected from the group consisting of the first organic moiety having structure (II) and the silicon-containing organic moiety having at least two carbons and having structure (IV).

[0062] In another aspect of the compositions of the invention described above, in structure (I), at least one of the moieties for R1, R2, R3, and R4 is selected from the group consisting of:

[0063] [ka] In another embodiment of the composition of the present invention described above, in structure (I), R1, R2, R3, and R4 are each independently selected from the group consisting of a first organic moiety having structure (II) and a silicon-containing organic moiety having at least two carbons and having structure (IV).

[0064] In another embodiment of the composition of the present invention, in structure (I), the silicon-containing organic moiety having at least two carbons and having structure (IV) is present in a range of 30 mol % to 60 mol % of the total number of moles of R1, R2, R3, and R4 of the metal compound having structure (I).

[0065] In another embodiment of the composition of the present invention, n is 2-20 in structure (I).

[0066] In another embodiment of the composition of the present invention described above, in structure (I), n is 1.

[0067] In another embodiment of the composition of the present invention, the first organic moiety having structure (II) is 10 Alkylene, C2-C containing C=C double bond 10 Alkylene, or C5-C 12 In another aspect of this embodiment, R5 is a C2-C 10In another aspect of this embodiment, R5 is a C2-C alkylene group containing a C=C double bond. 10 In yet another aspect, R5 is a C5-C alkylene. 12 It is a cycloalkylene.

[0068] In another embodiment of the above-described compositions of the invention, the first organic moiety has structure (II), wherein R6 is C1-C8 alkyloxycarbonyl. In another aspect of this embodiment, R6 is C2-C6 alkyloxycarbonyl. In yet another aspect, R6 is C3-C4 alkyloxycarbonyl.

[0069] In another embodiment of the above-described compositions of the invention, in the first organic moiety having structure (II), R6 has structure (III), where R7 is C1-C8 alkyl. In another aspect of this embodiment, R7 is C2-C6 alkyl. In yet another aspect, R7 is C3-C4 alkyl.

[0070] In another embodiment of the composition of the present invention described above, structure (IV) is where R8 is methyl, ethyl, propyl, butyl, or t-butyl.

[0071] In another embodiment of the composition of the present invention described above, structure (IV) is where R9 is methyl, ethyl, propyl, butyl, or t-butyl.

[0072] In another embodiment of the composition of the present invention, structure (IV) is a compound in which R8 is C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl.

[0073] In another embodiment of the composition of the present invention, structure (IV) is a compound in which R9 is C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl.

[0074] In another embodiment of the composition of the present invention, in structure (IV), R 10 is C1-C8 alkyl, C6-C 16 aryl, or hydroxyl.

[0075] In another embodiment of the composition of the present invention, in structure (IV), R 10 is C1 to C8 alkyl, or C6 to C 16 It is aryl.

[0076] In another embodiment of the composition of the present invention, in structure (IV), R 10 is a C1-C8 alkyl.

[0077] In another embodiment of the composition of the present invention, in structure (IV), R 10 is a siloxane having the structure (V).

[0078] In another embodiment of the composition of the present invention, structure (IV) is a compound in which R8 and R9 are C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl; R 10 is a siloxane having structure (V), where R 11 is a silyl moiety having structure (IVa), where R 8a and R 9a are C1-C8 alkyloxy and C3-C 12 branched alkyloxy, and R 10a But C6~C 16 Preferably, in this embodiment, R 12 and R 13 are each independently selected from the group consisting of C1-C8 alkyl.

[0079] In another embodiment of the composition of the present invention, in structure (IV), R8 and R9 are C1-C8 alkyloxy, C3-C12 Branched alkyloxy and C6-C 16 aryl; and R 10 C1-C8 alkyl, C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl.

[0080] In another embodiment of the composition of the present invention, in structure (IV), R 10 is methyl, ethyl, propyl, butyl or t-butyl.

[0081] In another embodiment of the composition of the present invention, in structure (IV), R 10 is a siloxane having the structure (V).

[0082] In another embodiment of the composition of the present invention, in structure (V), R 11 is C1-C8 alkyl or hydrogen. In another aspect of this embodiment, R 11 is C1-C4 alkyl or hydrogen. In yet another embodiment, R 11 is C1-C8 alkyl. In yet another embodiment, R 11 is C1-C4 alkyl. In yet another embodiment, R 11 is hydrogen.

[0083] In another embodiment of the composition of the present invention, in structure (V), R 12 is C1-C8 alkyl. In another aspect of this embodiment, R 12 is C1-C6 alkyl. In yet another embodiment, R 12 is C1-C4 alkyl.

[0084] In another embodiment of the composition of the present invention, in structure (V), R 13 is C1-C8 alkyl. In another aspect of this embodiment, R 13is C1-C6 alkyl. In yet another embodiment, R 13 is C1-C4 alkyl.

[0085] In another embodiment of the composition of the present invention described above, in structure (V), p is 1 to 500. In another aspect of this embodiment, p is 1 to 200. In yet another aspect, p is 1 to 50.

[0086] In another embodiment of the composition of the present invention, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups, wherein the structure is Structure (Ia1), Structure (Ia2), Structure (Ia3), or Structure (Ia4), where R 6a , R 6b and R 6c are independently selected from C1-C4 alkyl, further wherein n is independently an integer from 1 to 20. In another embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, when n is 2 to 20, the metal compound comprises a mixture of repeat units designated by n and the two end groups found in the structure above. In another embodiment of this aspect of the invention, n is 6 to 10.

[0087] [ka] In another embodiment of the composition of the present invention described above, it comprises a metal compound having the following structure, or a mixture thereof, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups, wherein the structure is Structure (Ib1), Structure (Ib2), Structure (Ib3), or Structure (Ib4), where n is independently an integer from 1 to 20. In one embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, when n is 2 to 20, the metal compound comprises a mixture of repeating units designated by n and the two end groups found in the above structures. In another preferred embodiment of this aspect of the invention, n is 6 to 10.

[0088] [ka] In another embodiment of the composition of the present invention, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups: Structure (Ic1), Structure (Ic2), Structure (Ic3), Structure (Ic4), Structure (Ic5), or Structure (Ic6), where R 11b is hydrogen, C1-C8 alkyl, C1-C8 alkyl substituted with hydroxyl, C6-C 16 aryl, and a silyl moiety having the structure (IVb), and R 6a , R 6b and R 6c is independently selected from C1-C4 alkyl, where n is independently an integer from 1 to 20, and p is independently an integer from 1 to 500. In another embodiment of this aspect of the invention, n is 1 to 20. In one embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, when n is 2 to 20, the metal compound comprises a mixture of repeat units designated by n and the two end groups found in the structure above.

[0089] [ka] In another embodiment of the composition of the present invention, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups: Structure (Id1), Structure (Id2), Structure (Id3), Structure (Id4), Structure (Id5), or Structure (Id6), where R 11a is a silyl moiety having structure (IVc), where n is independently an integer from 1 to 20, and p is independently an integer from 1 to 500. In one embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, when n is 2 to 20, the metal compound comprises a mixture of repeat units designated by n and the two end groups found in the structure above.

[0090] [ka] In another embodiment of the composition of the present invention, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups: Structure (Ie1), Structure (Ie2), Structure (Ie3), or Structure (Ie4), where R 6a is selected from C1-C4 alkyl, and R 8a and R 9a are C1-C8 alkyl and C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl; and R 10a is C1 to C8 alkyl and C6 to C 16aryl, where n is independently an integer from 1 to 20. In one embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, when n is 2 to 20, the metal compound comprises a mixture of repeat units designated by n and the two end groups found in the structure above.

[0091] [ka] In another embodiment of the composition of the present invention, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups: Structure (If1), Structure (If2), or Structure (If3), where R 6a is selected from C1-C4 alkyl, and R 8a and R 9a are C1-C8 alkyl and C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl, and R 10a is C1 to C8 alkyl and C6 to C 16 aryl, where n is 1 to 20. In one embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, when n is 2 to 20, the metal compound comprises a mixture of repeat units designated by n and the two end groups found in the structure above.

[0092] [ka] In another embodiment of the composition of the present invention, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups: Structure (Ig1), Structure (Ig2), Structure (Ig3), or Structure (Ig4), where R 6a is selected from C1-C4 alkyl, and R 8a and R 9a are C1-C8 alkyl and C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl, and R 10a is C1 to C8 alkyl and C6 to C 16 aryl, where n is 1 to 20. In one embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, when n is 2 to 20, the metal compound comprises a mixture of repeat units designated by n and the two end groups found in the structure above.

[0093] [ka] In another embodiment of the composition of the invention described above, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups, where the structure is structure (Ih1), structure (Ih2), structure (Ih4), or structure (Ih3), and n is 1 to 20. In one embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, when n is 2 to 20, the metal compound comprises a mixture of repeating units designated by n and the two end groups found in the above structures.

[0094] [ka] In another embodiment of the composition of the present invention, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups: Structure (Ii1), Structure (Ii2), Structure (Ii3), or Structure (Ii4), where R 6a and R 6d are independently selected from C1-C4 alkyl, and R 8a and R 9a are C1-C8 alkyl and C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl; and R 10a is C1 to C8 alkyl and C6 to C 16 aryl, where n is 1 to 20. In one embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, when n is 2 to 20, the metal compound comprises a mixture of repeat units designated by n and the two end groups found in the structure above.

[0095] [ka] In another embodiment of the composition of the invention described above, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups, where the structure is Structure (Ij1), Structure (Ij2), Structure (Ij3), or Structure (Ij4), and n is 1 to 20. In one embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, when n is 2 to 20, the metal compound comprises a mixture of repeating units designated by n and the two end groups found in the above structures.

[0096] [ka] In another embodiment of the composition of the present invention, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups: Structure (Ik1), Structure (Ik2), Structure (Ik3), or Structure (Ik4), where R 6a is selected from C1-C4 alkyl, and R 8a and R 9a are C1-C8 alkyl and C3-C 12 Branched alkyl, C1-C8 alkyloxy, C3-C 12 Branched alkyloxy and C6-C 16 aryl; and R 10a is a C1-C8 alkyl, where n is 6 to 20. In yet another embodiment, when n is 6 to 20, the metal compound comprises a mixture of repeat units designated by n and the two end groups found in the structure above.

[0097] [ka] In another embodiment of the composition of the present invention, it comprises a metal compound having the following structure, or a mixture of compounds having these structures, each of which comprises a repeating unit designated by n (the number of repeating units) and two end groups, where the structure is structure (Il1), structure (Il2), structure (Il3), or structure (Il3), and n is 1 to 20, preferably 6 to 20. In yet another embodiment, when n is 6 to 20, the metal compound comprises a mixture of repeating units designated by n and the two end groups found in the structures above.

[0098] [ka] In another embodiment of the composition of the present invention, the weight percent of the metal compound of component a) is about 20% to about 98% by weight of the total weight percent of all solid components, when component c) polyol is present. In another aspect of this embodiment, the weight percent of the total solid components is about 25% to about 80% by weight. In another aspect of this embodiment, the weight percent of the total solid components is about 30% to about 70% by weight. In another aspect of this embodiment, the weight percent of the total solid components is about 35% to about 65% by weight. In another aspect of this embodiment, the weight percent of the total solid components is about 40% to about 60% by weight. In another aspect of this embodiment, the weight percent of the total solid components is about 45% to about 60% by weight. In another aspect of this embodiment, the weight percent of the total solid components is about 50% to about 60% by weight. In another aspect of this embodiment, the weight percent of the total solids content is from about 55% to about 60%.

[0099] In another preferred embodiment of the composition of the present invention, when component c) polyol is present, the weight percent of component a) metal compound is about 20% to about 85% by weight. In another aspect of this embodiment, the weight percent of total solids component a) is about 30% to about 80% by weight. In another aspect of this embodiment, the weight percent of total solids component a) is about 50% to about 75% by weight.

[0100] In all of the above embodiments in which component c), a polyol, is present, the combined total solids content adds up to 100% by weight when no additional solid components are present. When additional solid components are present, the total solids weight % of the total solids of components a), b), c), and the additional component(s) adds up to 100% by weight of the total solids when no additional solid components are present. When additional solid components are present, the total solids weight % of the total solids of components a), b), c), and the additional component(s) adds up to 100% by weight of the total solids.

[0101] In another embodiment of the composition of the present invention described above, the weight percent of the metal compound of component a) is about 20% to about 98% by weight, based on the total weight percent of all solid components, when component c) polyol is not present. In another aspect of this embodiment, the weight percent of all solid components is about 25% to about 80% by weight. In another aspect of this embodiment, the weight percent of all solid components is about 30% to about 70% by weight. In another aspect of this embodiment, the weight percent of all solid components is about 35% to about 65% by weight. In another aspect of this embodiment, the weight percent of all solid components is about 40% to about 60% by weight. In another aspect of this embodiment, the weight percent of all solid components is about 45% to about 55% by weight. In another aspect of this embodiment, the weight percent of all solid components is from about 50% by weight. In all of the above embodiments where component c) is not present, the total combined solids weight % of component a) and component b) when no other additional solid components are present. When additional solid components are present, the total solids weight % of all solids of component a), component b) and any additional other component(s) adds up to 100% by weight of total solids.

[0102] Component b), a spin-on high carbon polymer In another aspect of the composition of the present invention, component b) is a spin-on high carbon polymer having a polymer backbone that includes both monocyclic aromatic hydrocarbon moieties and fused ring cyclic hydrocarbon moieties.

[0103] In another aspect of the composition of the present invention, component b) is a spin-on high carbon polymer having a polymer backbone containing only monocyclic aromatic hydrocarbon moieties.

[0104] In another aspect of the composition of the present invention, component b) is a spin-on high carbon polymer having a polymer backbone that contains only fused ring cyclic hydrocarbon moieties.

[0105] In one aspect of the composition of the present invention, in component b), the monocyclic aromatic hydrocarbon moiety is a phenylene or a substituted phenylene containing one or more such phenylene moieties, which are bonded to the polymer backbone directly to other aromatic hydrocarbon moieties or through one or more alkylene moieties that may contain the monocyclic aromatic hydrocarbon. Non-limiting examples of phenylene moieties containing alkylene moieties include (-alkylene-phenylene-), (-alkylene-phenylene-alkylene-), and (-phenylene-alkylene-phenylene-). The intermediate alkylene spacer may be selected from linked linear, branched, or cyclic moieties that may also contain an aromatic moiety, either a phenylene-containing moiety or a fused aromatic moiety-containing moiety. These monocyclic aromatic hydrocarbon moieties may be further substituted, either on the aromatic ring or on the alkylene portion, with linear or branched alkyl moieties, aryl moieties, fused aromatic moieties, or cyclic alkyl moieties (which may or may not contain olefinic or aromatic unsaturation as part of the alkyl portion), in addition to alkynyloxy substituents present due to capping of phenols with alkynyl moieties or any uncapped free phenols. Non-limiting examples of monocyclic aromatic hydrocarbon moieties are:

[0106] [ka] In one aspect of the composition of the present invention, in the spin-on high-carbon polymer of component b), the fused-ring hydrocarbon moiety is composed of one or more fused rings, which are either directly bonded to other aromatic rings in the main chain or indirectly bonded to other aromatic hydrocarbon moieties via one or more alkylene moieties that may contain the fused-ring hydrocarbon moiety. Non-limiting examples of such fused-ring hydrocarbon moieties containing alkylene moieties are (-alkylene-fused-ring-) moieties, (-alkylene-fused-ring-) moieties, (fused-ring-alkylene-fused-ring-) moieties, and the like. The intermediate alkylene spacer may be selected from linear, branched, or cyclic moieties, optionally substituted with phenyl- or fused aromatic-containing moieties. The fused ring hydrocarbon moiety may be further substituted, either on the aromatic ring or on the alkylene portion, with a linear or branched alkyl moiety, an aryl moiety, a fused aromatic moiety, or a cyclic alkyl moiety (which may or may not contain olefinic or aromatic unsaturation as part of the alkyl moiety), in addition to alkynyloxy substituents present due to capping of the phenol with an alkynyl moiety or any uncapped phenols. Non-limiting examples of fused ring hydrocarbon moieties are:

[0107] [ka] In one aspect of the composition of the present invention, component b) is one in which the fused ring hydrocarbon moiety comprises a fused aromatic moiety having 2 to 8 rings. In another aspect of this embodiment, the fused ring hydrocarbon moiety comprises a fused aromatic moiety having 2 to 5 rings.

[0108] In one aspect of component b) of the compositions of the present invention, the monocyclic aromatic hydrocarbon moiety and the fused ring cyclic hydrocarbon moiety may be selected from the group consisting of:

[0109] [ka] and mixtures thereof.

[0110] In the embodiments described herein for component b), the material may contain some free phenolic OH groups that are not capped with alkynyl moieties forming the alkynyloxy moieties of structure (VIII). However, it is preferred that the molar ratio of free phenol to phenols capped with alkynyl moieties forming the alkynyloxy moieties of structure (VIII) be no higher than about 50:50. In other aspects of the invention, this ratio can be even lower, specifically, in one embodiment, about 40:60 or less, in yet another aspect about 30:70 or less, in yet another aspect about 20:80 or less, in yet another aspect about 10:90 or less, in yet another aspect about 5:95 or less, and finally, in another embodiment, no significant amount of free phenol is present, and all phenolic moieties are capped with alkynyl moieties to form the alkynyloxy moieties of structure (VIII).

[0111] In another embodiment of the composition of the present invention, component b) of the spin-on high-carbon polymer comprises a moiety having a phenolic group that is capped to form an alkynyloxy moiety of structure (VIII), which may be selected from the group consisting of (IX), (IXa), (IXb), (IXc), (IXd), (IXe), (IXf), (IXg), (IXh), (IXi), and mixtures thereof. Other types of optional moieties may also be present in this component. For example, uncapped moieties having a free phenolic group corresponding to moieties (IX), (IXa), (IXb), (IXc), (IXd), (IXe), (IXf), (IXg), (IXh), and (IXi) may be present in a molar ratio to the alkynyloxy group as described above. Other types of optional moieties that may be present are those in which the alkynyloxy groups in moieties (IX), (IXa), (IXb), (IXc), (IXd), (IXe), (IXf), (IXg), (IXh), and (IXi) are replaced with hydrogen, aryl, or C1-C6 alkyl groups; these types of moieties may be present in amounts up to about 20 mol % of the total moieties in the high carbon component b), and in other respects, they are present in amounts up to about 10 mol %, in yet other respects, up to 5 mol %, and in yet other respects, up to 1 mol %.

[0112] [ka] In another embodiment of the composition of the present invention, component b) comprises a repeating unit having the structure (X):

[0113] [ka] In this embodiment, A is selected from the group consisting of moieties (IX), (IXa), (IXb), (IXc), (IXd), (IXe), (IXf), (IXg), (IXh), (IXi), and mixtures thereof, and B is a moiety selected from the group consisting of (Xa), (Xb), (Xc), (Xd), and mixtures thereof, wherein R x1 and R x2are independently hydrogen, a C1-C6 alkyl, an aryl moiety, or an alkynyloxy moiety of structure (VIII). Similarly, in this aspect of component b), optional repeat units can be present in which alkynyloxy groups in said selected moieties in A are replaced with hydroxy groups in the molar ratios described above. Additionally, in other optional repeat units, alkynyloxy groups in said selected moieties for A can be replaced with hydrogen, aryl, or C1-C6 alkyl groups, and such optional moieties can be present in up to about 20 mole % of the total in component b), in one other aspect they are present in up to about 10 mole %, in yet another aspect up to 5 mole %, and in yet another aspect up to 1 mole %.

[0114] [ka] In another embodiment of the composition of the present invention described above, the spin-on high carbon polymer of component b) comprises repeat units having structure (XI). In another aspect of this embodiment, the spin-on high carbon polymer comprises repeat units having structure (XIa). In yet another aspect of this embodiment, the spin-on high carbon polymer comprises repeat units having structure (XIb). Similarly, in this embodiment of component b), optional repeat units can be present in which alkynyloxy groups in these repeat units are replaced with hydroxy groups in the molar ratios described above. Additionally, in other optional repeat units, the alkynyloxy groups in these repeat units may be replaced with hydrogen, aryl, or C1-C6 alkyl groups, and such optional repeat units may be present in component b) in an amount up to about 20 mole % of the total, in one aspect they are present in an amount up to about 10 mole %, in one aspect up to 5 mole %, and in one aspect up to 1 mole %.

[0115] [ka] In another embodiment of the inventive composition, in component b), the spin-on high-carbon polymer comprises repeat units having structure (XIc). In another aspect of this embodiment, the spin-on high-carbon polymer comprises repeat units having structure (XId). Similarly, in these embodiments of component b), optional repeat units can be present in which the alkynyloxy groups in these repeat units are replaced with hydroxy groups in the molar ratios described above. Additionally, in other optional repeat units, the alkynyloxy groups in these repeat units can be replaced with hydrogen, aryl, or C1-C6 alkyl groups, and such optional repeat units can be present in component b) in an amount of up to about 20 mol % of the total; in another aspect, they are present in an amount of up to about 10 mol %, in yet another aspect, up to 5 mol %, and in yet another aspect, up to 1 mol %.

[0116] [ka] In another aspect of the inventive composition, the spin-on high carbon polymer of component b) comprises repeating units of structure (XII), where fAr is a fused aromatic ring and R 16 and R 17are each independently hydrogen or C1-C4 alkyl. In another aspect of this embodiment, fAr is a group containing 2 to 8 fused aromatic rings. In yet another aspect of this embodiment, fAr is anthracene. In yet another aspect of this embodiment, the repeat unit has structure (XIIa). In yet another aspect, the repeat unit has structure (XIIb). In yet another aspect, the repeat unit has structure (XIIc). Similarly, in these embodiments of component b), optional repeat units can be present in which alkynyloxy groups in these repeat units are replaced with hydroxy groups in the molar ratios described above. Additionally, in other optional repeat units, the alkynyloxy groups in these repeat units may be replaced with hydrogen, aryl, or C1-C6 alkyl groups, and such optional repeat units may be present in component b) in an amount up to about 20 mole % of the total, in one aspect they are present in an amount up to about 10 mole %, in one aspect up to 5 mole %, and in one aspect up to 1 mole %.

[0117] [ka] In another aspect of the composition of the present invention, the spin-on high carbon polymer of component b) comprises repeating units selected from the group consisting of repeating units having structures (XIII), (XIIIa), (XIIIb), (XIIIc), and (XIIId) and mixtures thereof. In another aspect of this embodiment, it comprises repeating units selected from the group consisting of repeating units having structures (XIIIe), (XIIIf), (XIIIg), (XIIIh), and (XIIIi) and mixtures thereof. In another aspect of this embodiment, R 16 and R 17 is C1-C6 alkyl. In yet another embodiment, R 16 and R 17 is C1-C4 alkyl. In yet another embodiment, R 16 and R 17 is hydrogen. In yet another embodiment, R 16and R 17 is methyl. In yet another embodiment, R a1 , R a2 and R a3 is hydrogen. Similarly, in these embodiments of component b), optional repeat units can be present in which the alkynyloxy groups in these repeat units are replaced with hydroxy groups in the molar ratios described above. Additionally, in other optional repeat units, the alkynyloxy groups in these repeat units can be replaced with hydrogen, aryl, or C1-C6 alkyl groups, and such optional repeat units can be present in component b) in an amount of up to about 20 mol % of the total; in one aspect, they are present in an amount of up to about 10 mol %, in yet another aspect, up to 5 mol %, and in yet another aspect, up to 1 mol %.

[0118] [ka] In another aspect of the composition of the present invention, the spin-on high carbon polymer of component b) comprises a selected repeat unit having structure (XIV). In another aspect of this embodiment, it comprises a repeat unit selected from the group consisting of repeat units having structure (XIVa). In another aspect, R a1 , R a2 and R a3 is hydrogen. Similarly, in these embodiments of component b), optional repeat units can be present in which the alkynyloxy groups in these repeat units are replaced with hydroxy groups in the molar ratios described above. Additionally, in other optional repeat units, the alkynyloxy groups in these repeat units can be replaced with hydrogen, aryl, or C1-C6 alkyl groups, and such optional repeat units can be present in component b) in an amount of up to about 20 mol % of the total; in one aspect, they are present in an amount of up to about 10 mol %, in yet another aspect, up to 5 mol %, and in yet another aspect, up to 1 mol %.

[0119] [ka] In any of the compositions of the invention described herein, the spin-on high carbon polymer of component b) has a Mw of about 500 to about 5000. In another aspect of this embodiment, the high carbon polymer has a Mw of about 600 to about 3000. In yet another aspect of this embodiment, it has a Mw of about 600 to about 2500. In yet another aspect of this embodiment, it has a Mw of about 600 to about 2300. In yet another embodiment, it has a Mw of about 600 to about 2200. In yet another embodiment, it has a Mw of about 600 to about 2000. In yet another embodiment, it has a Mw of about 600 to about 1500. In yet another embodiment, it has a Mw of about 600 to about 1300. In yet another embodiment, it has a Mw of about 700 to about 1200.

[0120] In another aspect of the composition of the present invention, the spin-on high carbon polymer of component b) is an alkynyloxy-substituted spin-on carbon polymer present in an amount of from about 1% up to about 50% by weight of the metal compound.

[0121] In another embodiment of the composition of the present invention described above, when component c) polyol is present, component b) alkynyloxy-substituted spin-on carbon polymer is present in an amount of from about 1 wt % to about 50 wt %, based on the weight percent of total solids. b In another aspect of this embodiment, the component b In another aspect of this embodiment, the component b In another aspect of this embodiment, the component b In another aspect of this embodiment, the component bIn another aspect of this embodiment, the component b In another aspect of this embodiment, the component b ) is present at about 25% to about 35% by weight. In all aspects of these embodiments, the total weight percent of the solid components of components a), b), and c) adds up to 100% by weight when no additional solid components are present. When additional solid components are present, the total solids weight percent of the total solids of component a), component c), component b), and the additional component(s) adds up to 100% by weight of the total solids.

[0122] In another embodiment of the composition of the present invention described above, when component c) is absent, the alkynyloxy-substituted spin-on carbon polymer additive is present in an amount, expressed as a weight percent of total solids, of about 1 wt % to about 60 wt %. In another aspect of this embodiment, component b) is present in an amount of about 5 wt % to about 60 wt %. In another aspect of this embodiment, component b) is present in an amount of about 10 wt % to about 60 wt %. In another aspect of this embodiment, component b) is present in an amount of about 15 wt % to about 55 wt %. In another aspect of this embodiment, component b) is present in an amount of about 20 wt % to about 55 wt %. In another aspect of this embodiment, component b) is present in an amount of about 25 wt % to about 55 wt %. In another aspect of this embodiment, component b) is present in an amount of about 30 wt % to about 55 wt %. In another aspect of this embodiment, component b) is present in an amount of about 35 wt % to about 55 wt %. In another aspect of this embodiment, component b) is present in an amount of about 40 wt % to about 55 wt %. In another aspect of this embodiment, component b) is present at about 45% to about 55% by weight. In another aspect of this embodiment, component b) is present at about 50% by weight. In all aspects of these embodiments, when component c) is absent, the total weight percent of components a) and c) of the solid components adds up to 100% by weight in the absence of other additional solid components. When additional solid components are present, the total solids weight percent of all solids of component a), component b), and any other additional component(s) adds up to 100% by weight of total solids.

[0123] Specific non-limiting examples of formulations according to the present invention are: A non-limiting composition includes component b), whose polymer comprises repeating units of structure (XIb), and component a), which is comprised of the group consisting of metal compounds having structures (Il1), (Il2), (Il3), (Il4), or mixtures thereof, where n is 6-20. In one specific embodiment, the formulation includes an approximately 50:50 ratio of components a) and b). In another embodiment, the formulation includes an approximately 80:20:40 ratio of components a):optional component c):component b), where optional component c) is triethanolamine.

[0124] Non-limiting compositions include component b), whose polymer comprises repeating units of structure (XId), and component a), which is comprised of the group consisting of metal compounds having structures (Il1), (Il2), (Il3), (Il4), or mixtures thereof, where n is 6-20. In one specific embodiment, the formulation comprises about a 50:50 ratio of components a) and b). In another embodiment, the formulation comprises about an 80:20:40 ratio of components a):optional component c):component b), where optional component c) is triethanolamine.

[0125] A non-limiting composition includes component b), where the polymer comprises repeating units of structure (XIIc), and component a), which is comprised of a metal compound selected from the group consisting of metal compounds having structures (Il1), (Il2), (Il3), (Il4), and mixtures thereof, where n is 6-20. In one specific embodiment, the formulation includes an approximately 50:50 ratio of components a) and b). In another embodiment, the formulation includes an approximately 80:20:40 ratio of components a):optional component c):component b), where optional component c) is triethanolamine.

[0126] A non-limiting composition includes component b), where the polymer comprises repeating units of structure (XIIIc), and component a), which is comprised of a metal compound selected from the group consisting of metal compounds having structures (Il1), (Il2), (Il3), (Il4), and mixtures thereof, where n is 6-20. In one specific embodiment, the formulation includes an approximately 50:50 ratio of components a) and b). In another embodiment, the formulation includes an approximately 80:20:40 ratio of components a):optional component c):component b), where optional component c) is triethanolamine.

[0127] Component b) wherein the polymer comprises repeating units of structural units having the structures (XIIIe), (XIIIf), (XIIIg), (XIIIh), (XIIIi), and mixtures thereof (wherein R 16 and R 17 is methyl, and R a1 , R a2 and R a3 is hydrogen) and component a) comprised of a metal compound selected from the group consisting of metal compounds having structures (II1), (II2), (II3), (II4), and mixtures thereof, where n is 6-20. In one specific embodiment, the formulation comprises an approximately 50:50 ratio of components a) and b). In another embodiment, it comprises an approximately 80:20:40 ratio of components a):optional component c):component b), where optional component c) is triethanolamine.

[0128] Component b) (wherein the polymer comprises repeating units of structural units having structures (XIV), (XVa), and mixtures thereof) a1 , R a2 and R a3is hydrogen) and component a) comprised of a metal compound selected from the group consisting of metal compounds having structures (II1), (II2), (II3), (II4), and mixtures thereof, where n is 6-20. In one specific embodiment, the formulation comprises an approximately 50:50 ratio of components a) and b). In another embodiment, it comprises an approximately 80:20:40 ratio of components a):optional component c):component b), where optional component c) is triethanolamine.

[0129] Other similar non-limiting examples of compositions according to the invention correspond to the above non-limiting examples, but in which the described component a) is in each case: Structure (Id1), Structure (Id2), Structure (Id3), Structure (Id4), Structure (Id5), or Structure (Id6) (However, R 11a is a silyl moiety having the structure (IVc), n is independently an integer from 1 to 20, and p is independently an integer from 1 to 500; Component a) consisting of a mixture of metal complexes having Structure (If1), Structure (If2), Structure (If3), and Structure (If4), where n is 1 to 20. (In another embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, n is 2 to 20.) Component a) consisting of a mixture of metal complexes having Structure (Ih1), Structure (Ih2), Structure (Ih3), and Structure (Ih4), where n is 1 to 20. In another embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, n is 2 to 20. Component a) consisting of a mixture of metal complexes having Structure (Ij1), Structure (Ij2), Structure (Ij3), and Structure (Ij4) (wherein n is 1 to 20) (in another embodiment of this aspect of the invention, n is 6 to 20. In another embodiment of this aspect of the invention, n is 1. In yet another embodiment, n is 2 to 20); wherein the metal complex is replaced by another metal complex a) selected from the group consisting of:

[0130] Optional Component c), Polyol In one embodiment of the composition of the present invention described above, component c) a polyol is present.

[0131] In another embodiment of the composition of the present invention described above, in the polyol additive having structure (VI) of component c), this embodiment is one in which X is C.

[0132] In another embodiment of the composition of the present invention described above, in the polyol additive having structure (VI) of component c), this embodiment is one in which X is N.

[0133] In another embodiment of the composition of the present invention described above, for the polyol additive having structure (VI) of component c), this embodiment is one in which Y is a direct bond, methylene, ethylene, or a moiety having structure (VII).

[0134] In another embodiment of the composition of the present invention described above, in the polyol additive having structure (VI) of component c), this embodiment is one in which r is 2, 3, or 4.

[0135] In another embodiment of the composition of the present invention described above, in the polyol additive having structure (VI) of component c), this embodiment is 14 is hydrogen.

[0136] In another embodiment of the composition of the present invention described above, in component c) the polyol additive having structure (VI), this embodiment is one in which q is 0, 1 or 2.

[0137] In another embodiment of the composition of the present invention described above, in the polyol additive having structure (VI) of component c), this embodiment is one in which s is 0 or 2.

[0138] In another embodiment of the composition of the present invention described above, in the polyol additive having structure (VI) of component c), this embodiment is one in which s is 0.

[0139] In another embodiment of the composition of the present invention described above, in the polyol additive having structure (VI) of component c), this embodiment is one in which s is 2.

[0140] In another embodiment of the composition of the present invention described above, in the polyol additive having structure (VI) of component c), this embodiment is one in which s is 1.

[0141] In another embodiment of the composition of the present invention described above, in the polyol additive having structure (VI) of component c), when X is N and Y is C1-C8 alkylene, or when X is C and Y is selected from the group consisting of a direct valence bond, a C1-C8 alkylene, and a moiety having structure (VII), this embodiment can be further modified by adding R 15 is ethylene or propylene.

[0142] In another embodiment of the composition of the present invention described above, in the polyol additive having structure (VI) of component c), when X is N and Y is C1-C8 alkylene, or when X is C and Y is selected from the group consisting of a direct valence bond, a C1-C8 alkylene, and a moiety having structure (VII), this embodiment is one in which t is 1.

[0143] In another embodiment of the composition of the present invention, in component c), the polyol additive is selected from the group consisting of tetraethylene glycol, triethylene glycol, glycerol, triethanolamine, diethanolamine, neopentyl glycol, glycerol propoxylate, and pentaerythritol ethoxylate.

[0144] In another embodiment of the composition according to the invention, when component c) is present, this embodiment is such that the polyol additive is selected from:

[0145] [ka] In another embodiment of the composition of the present invention described above, component c), if present, is selected from the group consisting of:

[0146] [ka] In another embodiment of the composition of the present invention described above, component c is selected from:

[0147] [ka] In another embodiment of the composition of the present invention described above, component c is selected from:

[0148] [ka] In another preferred embodiment of the compositions of the present invention described above, the weight percent of component c), a polyol, when present, as a weight percent of all solid components is about 1 weight percent to about 30 weight percent. In another aspect of this embodiment, the weight percent of all solid components is about 5 weight percent to about 30 weight percent. In another aspect of this embodiment, this weight percent of component c), as a weight percent of all solid components, is about 10 weight percent to about 25 weight percent. In another aspect of this embodiment, this weight percent of component c), as a weight percent of all solid components, is about 10 weight percent to about 20 weight percent. In another aspect of this embodiment, this weight percent of component c), as a weight percent of all solid components, is about 12 weight percent to about 15 weight percent. In all of the above embodiments in which component c) is present, the overall total solids content, in the absence of additional components, is 100 weight percent of total solids. If additional ingredients are present, the total solids weight % of the total solids of component a), component b), component c) and any of these additional ingredient(s) adds up to 100% by weight of the total solids.

[0149] In another embodiment of the composition according to the invention, in component c), the polyol additive has a molecular weight of less than 500.

[0150] In another embodiment of the composition according to the invention, in component c), the polyol additive has a molecular weight of less than 300.

[0151] In another embodiment of the composition according to the invention, in component c), the polyol additive has a boiling point of at least 200°C.

[0152] In another embodiment of the composition according to the invention, the polyol additive has a boiling point of at least 250°C.

[0153] In another embodiment of the composition according to the invention, the polyol additive has a boiling point of at least 400°C.

[0154] In another embodiment of the inventive composition described above, the alkynyloxy-substituted spin-on carbon polymer of component b) is selected from the group consisting of polyethers, polyesters, polysulfones, and polyethersulfones.

[0155] Component d), solvent The solvent is typically a solvent or mixture of solvents containing alcohols, esters, ketones, lactones, and / or diketones. Additional components (<1%) such as surfactants can be added to improve the coating quality. The composition of the baked film under these conditions contains 20-70% total oxides.

[0156] In the novel composition, the solid components may be dissolved in an organic solvent, solvent component f). Examples of suitable organic solvents include, but are not limited to, 1-methoxy-2-propanyl acetate (PGMEA), 1-methoxy-2-propanol (PGME), butyl acetate, amyl acetate, cyclohexyl acetate, 3-methoxybutyl acetate, methyl ethyl ketone, methyl amyl ketone, cyclohexanone, cyclopentanone, ethyl 3-ethoxypropanoate, methyl 3-ethoxypropanoate, methyl 3-methoxypropanoate, methyl acetoacetate, ethyl acetoacetate, diacetone alcohol, methyl pivalate, ethyl pivalate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monomethyl ether propanoate, propylene glycol monoethyl ether propanoate, and propylene glycol monoethyl ether propanoate. Examples of suitable solvents include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, 3-methyl-3-methoxybutanol, N-methylpyrrolidone, dimethyl sulfoxide, gamma-butyrolactone, gamma valerolactone, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, methyl lactate, ethyl lactate, propyl lactate, tetramethylene sulfone, propylene glycol dimethyl ether, dipropylene glycol dimethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, and anisole. These solvents may be used alone or as a mixture of two or more.

[0157] In one embodiment, the solid components are dissolved in PGMEA / PGME 70:30.

[0158] In another embodiment of the above inventive composition, component d, the solvent, is selected from the group consisting of alcohols, esters, ketones, lactones, diketones, aromatic moieties, carboxylic acids, amides, and mixtures thereof. In one embodiment, the solvent is cyclohexanone.

[0159] Other optional ingredients In another embodiment of the compositions of the present invention described above, in addition to components a), b), c) and d), these compositions may further comprise at least one additional component selected from the group consisting of surfactants, leveling agents, crosslinking additives and heat-activated catalysts.

[0160] Optional Surfactant Optional ingredients such as surfactants can be added in small amounts, such as at concentrations of less than 1% by weight, to improve the quality of the coating.

[0161] More specifically, other optional components that are compatible with and can be added as needed to the novel compositions disclosed and claimed herein include auxiliary resins, plasticizers, surface leveling agents, and stabilizers to improve the properties of the coated composition on the surface, etc. Surface leveling agents can include surfactants, etc. The surfactant is not particularly limited, and examples thereof include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene olein ether; polyoxyethylene alkylaryl ethers such as polyoxyethylene octylphenol ether and polyoxyethylene nonylphenol ether; polyoxyethylene polyoxypropylene block copolymers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, and sorbitan monostearate; nonionic surfactants of polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyethylene sorbitan trioleate, and polyoxyethylene sorbitan tristearate; fluorinated surfactants such as F-Top EF301, EF303, and EF352 (manufactured by Gemco), Megafac F171, F172, F173, R08, R30, R90 and R94 (manufactured by DIC Corporation), Florad FC-430, FC-431, FC-4430 and FC-4432 (manufactured by Sumitomo 3M Limited), Asahi Guard AG710, Surflon S-381, S-382, S-386, SC101, SC102, SC103, SC104, SC105, SC106, Surfinol E1004, KH-10, KH-20, KH-30 and KH-40 (manufactured by AGC Corporation); organosiloxane polymers such as KP-341, X-70-092 and X-70-093 (manufactured by Shin-Etsu Chemical Co., Ltd.); and acrylic or methacrylic acid polymers such as Polyflow No. 75 and No. 95 (manufactured by Kyoeisha Chemical Co., Ltd.).

[0162] In another embodiment of the composition according to the invention, the surfactant is present in an amount of less than 1% of the total weight of the composition.

[0163] Optional Crosslinker A crosslinking agent can be added to improve the coating forming properties of the coating to be formed, to prevent intermixing with the upper layer (e.g., the silicon-containing intermediate layer and the resist), and to prevent diffusion of low molecular weight components into the upper layer.

[0164] Exemplary embodiments of crosslinking agents that can be used in the present invention include melamine, guanamine, glycoluril, and urea compounds substituted with at least one group selected from methylol groups, alkoxymethyl groups, and acyloxymethyl groups; epoxy compounds; thioepoxy compounds; isocyanate compounds; azide compounds; and compounds having double bond-containing groups such as alkenyl ether groups. These may be used as additives or, alternatively, may be introduced as pendant groups into polymer side chains. Compounds containing hydroxy groups may also be used as crosslinking agents.

[0165] Examples of the epoxy compounds include tris(2,3-epoxypropyl) isocyanurate, trimethylolmethane triglycidyl ether, trimethylolpropane triglycidyl ether, and triethylolethane triglycidyl ether. Exemplary embodiments of the melamine compounds include hexamethylolmelamine, hexamethoxymethylmelamine, and any mixture of such compounds. Examples of the guanamine compounds include tetramethylolguanamine, tetramethoxymethylguanamine, and any mixture of such compounds. Examples of the glycoluril compounds include tetramethylolglycoluril, tetramethoxyglycoluril, tetramethoxymethylglycoluril, and any mixture of such compounds. Examples of the urea compounds include tetramethylolurea and tetramethoxymethylurea.

[0166] Examples of the compound containing an alkenyl ether group include ethylene glycol divinyl ether and triethylene glycol divinyl ether.

[0167] Examples of crosslinkers for use in the present invention include those represented by structure (XV).

[0168] [ka] In structure (XV), L3 is a direct bond, a substituted or unsubstituted C 1-3 Alkyl, or substituted or unsubstituted C 7-16 L3 is preferably a direct bond, a C1 alkyl, or a C 15 The alkyl or aralkyl substituents are preferably hydrogen, methyl, C 6-11 In a preferred aspect, L3 is an unsubstituted C 1-3 Alkyl or unsubstituted C 1-3 It is aralkyl.

[0169] [ka] In structure (XV), R 11 is hydrogen or methyl.

[0170] The following are exemplary embodiments of cross-linkers represented by structure (XV): The scope of the present invention is not limited thereto.

[0171] [ka] The following are exemplary embodiments of other crosslinkers that may be included in the planarizing coating-forming composition, without the scope of the present invention being limited thereto:

[0172] [ka] These crosslinking agents are available from, for example, Sanwa Chemical Co., Ltd., Honshu Chemical Industry Co., Ltd., Asahi Organic Chemicals Co., Ltd., and Nippon Carbide Industries Co., Ltd.

[0173] In one embodiment of the present invention, the amount of the crosslinking agent is preferably 0 to 300,000 ppm by mass of the total composition. When the composition contains a crosslinking agent, the amount thereof is preferably 0.1 to 100,000 ppm, more preferably 1 to 50,000 ppm, and even more preferably 10 to 10,000 ppm.

[0174] The composition of the present invention can also exhibit its effects without adding an effective amount of a crosslinking agent. In this case, the amount of crosslinking agent relative to the mass of the total composition is preferably 0 to 20,000 ppm, more preferably 0 to 5,000 ppm, even more preferably 0 to 1,000 ppm, and still more preferably 0 to 100 ppm.

[0175] In one embodiment of the present invention, the amount of crosslinker is preferably 1 to 200% by weight (more preferably 5 to 100% by weight, even more preferably 10 to 40% by weight, even more preferably 15 to 25% by weight) based on the total weight of the inventive ethynyl-derived complex (or the total weight of two or more inventive ethynyl-derived complexes) contained in the composition. The incorporation of a crosslinker in the composition is expected to have the following effect: the crosslinker binds to the inventive ethynyl-derived complex during coating formation, controlling the intermolecular twist of the entire complex between the crosslinker and the compound and increasing the planarity of the complex.

[0176] Given the ease of process control, the present invention can be carried out in an embodiment in which the invented ethynyl-derived complex is formed into a coating by itself without adding a crosslinking agent (which means that the amount of crosslinking agent is 0% by weight relative to the weight of the invented ethynyl-derived complex).

[0177] Optional Acid Generator One embodiment of the composition according to the present invention can further comprise an acid generator, preferably in an amount of 0.1 to 10% by weight, more preferably 1 to 7% by weight, and even more preferably 1 to 5% by weight, based on the weight of the inventive ethynyl-derived complex (or the total weight of two or more inventive ethynyl-derived complexes).

[0178] The acid generator can be a thermal acid generator capable of generating a strong acid when heated. The thermal acid generator (TAG) used in one embodiment of the present invention can include one or more thermal acid generators that, when heated, generate an acid capable of reacting with the inventive ethynyl-derived complex and promoting crosslinking of the ethynyl-derived complex. The acid is more preferably a strong acid, such as a sulfonic acid. The thermal acid generator is preferably activated at a temperature above 80°C. Examples of thermal acid generators include metal-free sulfonium salts, such as triarylsulfonium, dialkylarylsulfonium, and diarylalkylsulfonium salts of strong non-nucleophilic acids; metal-free iodonium salts, such as alkylaryliodonium and diaryliodonium salts of strong non-nucleophilic acids; and ammonium, alkylammonium, dialkylammonium, trialkylammonium, and tetraalkylammonium salts of strong non-nucleophilic acids. Covalent acid generators are also believed to be useful as additives, and examples include 2-nitrobenzyl esters of alkyl or aryl sulfonic acids and other sulfonic acid esters that thermally decompose to the free sulfonic acid, such as diaryliodonium perfluoroalkyls and sulfonates. Examples of labile esters include nitrobenzyl tosylates, such as 2-nitrobenzyl tosylate, 2,4-dinitrobenzyl tosylate, 2,6-dinitrobenzyl tosylate, and 4-nitrobenzyl tosylate; benzenesulfonates, such as 2-trifluoromethyl-6-nitrobenzyl 4-chlorobenzenesulfonate and 2-trifluoromethyl-6-nitrobenzyl 4-nitrobenzenesulfonate; phenolic sulfonate esters, such as phenyl 4-methoxybenzenesulfonate; quaternary ammonium tris(fluoroalkylsulfonyl)methides; quaternary alkylammonium bis(fluoroalkylsulfonium)imides; and alkylammonium salts of organic acids, such as the triethylammonium salt of 10-camphorsulfonic acid.Various amine salts of aromatic (anthracene, naphthalene, or benzene derivative) sulfonic acids can be used as TAGs, including those described in US Pat. No. 3,474,054B, US Pat. No. 4,200,729B, US Pat. No. 4,251,665B, and US Pat. No. 5,187,019B.

[0179] The following are exemplary embodiments of thermal acid generators that may be included in the composition, but the scope of the present invention is not limited thereto:

[0180] [ka] Given the ease of process control, the present invention can be implemented in an embodiment in which no acid generator is added to the composition (which means that the amount of acid generator is 0% by weight relative to the weight of the invented ethynyl-derived complex).

[0181] In one embodiment of the present invention, the amount of the acid generator is preferably 0 to 50,000 ppm, more preferably 0 to 5,000 ppm, even more preferably 0 to 1,000 ppm, and still more preferably 0 to 100 ppm, based on the mass of the entire composition.

[0182] Optional Radical Generator To initiate polymerization, a radical generator can be added to the composition. The radical generator generates radicals when heated, and examples thereof include azo compounds and peroxides. Exemplary embodiments of the radical generator include organic peroxides, such as hydroperoxides, for example, diisopropylbenzene hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide, dialkyl peroxides, for example, α,α-bis(t-butylperoxy-m-isopropyl)benzene, dicumyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-butyl peroxide, and 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne. Examples of thermal radical generators include tert-butyl peroxy-2-ethylhexanoate, ketone peroxides, peroxyketals such as n-butyl 4,4-di(t-butylperoxy)valerate, diacyl peroxides, peroxydicarbonates, and peroxyesters; and azo compounds such as 2,2'-azobisisobutyronitrile, 1,1'-(cyclohexane-1-1-carbonitrile), 2,2'-azobis(2-cyclopropylpropionate), and 2,2'-azobis(2,4-dimethylvaleronitrile). These thermal radical generators can be used alone or in combination with others, and are preferably used alone. These known radical generators can be used in the composition, and these radical generators can be obtained, for example, from NOF.

[0183] Composition: Content of all solid components in the solvent In one embodiment, for these novel compositions, the weight percent total solids content of all solid components in the solvent ranges from about 1 wt % to about 40 wt % total solids in the solvent. In another embodiment, from about 2 wt % to about 40 wt %. In yet another embodiment of this aspect of the invention, from about 5 wt % to about 35 wt %. In yet another embodiment of this aspect of the invention, the weight percent solids content is from about 10 wt % to about 35 wt %. In yet another embodiment of this aspect of the invention, from about 10 wt % to about 35 wt %. In yet another embodiment of this aspect of the invention, the weight percent solids content is from about 15 wt % to about 30 wt %. In another embodiment, from about 20 wt % to about 30 wt %. In yet another embodiment of this aspect of the invention, the weight percent solids content is about 25 wt %.

[0184] Method of using the composition A method for filling voids in a substrate having a topographical feature.

[0185] One aspect of the present invention is a method for fabricating electronic devices by forming a patterned high-K material produced by filling voids, such as vias, in a patterned substrate via a coating process using any of the novel compositions described above. The patterned substrate may be a patterned semiconductor (e.g., silicon, germanium), a patterned spin-on carbon, or a patterned resist. The resulting patterned material, in addition to its use as a high-K material, may alternatively be used in the fabrication of electronic devices in the role of a hard mask. The patterned hard mask, due to the heat-resistant properties of the metal compounds contained in the compositions of the present invention, provides high etch resistance to various plasmas, allowing for etching and transfer of patterns into the substrate.

[0186] The novel compositions can be applied to a substrate (either unpatterned or patterned) to form a coating film as follows: a) applying any of the compositions of the present invention described above onto a substrate to form a coating film; and b) Heating the coating film at a temperature between 150°C and 400°C for a time period between 30 seconds and 240 seconds to form a cured coating film.

[0187] In another aspect of this embodiment, the coating film is heated for a time period of up to 120 seconds. In another aspect, the hard mask composition can be applied to the substrate by a spin-on coating method. In yet another aspect, the composition is applied to the substrate in step a) by a one-step spin-on coating method to form the coating film.

[0188] In one embodiment of this method for using the composition of the present invention as a gap-filling material, the substrate coated with the composition to form a coating film is a patterned substrate containing a topographical feature, in which the cured coating film formed in step b) is coated to a thickness sufficient to cover the topographical feature, and further wherein, after baking the film in step b), the method includes an additional step, step c), as follows:

[0189] c) removing the cured film overlying the topography using a chemical stripper or a fluorinated plasma etch, thereby producing a filled topography pattern, where the cured coating film is flush with the topography pattern.

[0190] In another embodiment of this gap-fill aspect of the method of the present invention, the topographical feature is in a patterned spin-on carbon layer overlying a silicon substrate. In another embodiment of this method, the topographical feature is in a patterned semiconductor, such as silicon, germanium, etc. In yet another embodiment, the topographical feature is in a patterned resist overlying the semiconductor substrate. In yet another embodiment of any of these gap-fill methods of the present invention, the topographical feature to be filled is a via. In yet another embodiment of any of these gap-fill methods, the topographical feature is a contact hole, a via, or a mixture thereof.

[0191] In any of these methods, in yet another aspect, when the topographical feature is a patterned photoresist or a patterned organic high carbon coating over a semiconductor substrate (e.g., silicon, germanium, etc.), the method further comprises, after step c), an additional step, step d), of: d) removing the patterned organic high-carbon coating or the patterned photoresist with an oxygen plasma, thereby forming a negative tone image of the patterned photoresist or the patterned organic high-carbon coating, wherein the remaining filled topographical features form a pattern comprised of metal oxide after removal of the patterned photoresist or the patterned organic high-carbon coating. In one aspect of the invention, this pattern comprised of metal oxide is useful as a patterned high-K material or for the fabrication of microelectronic components incorporating such K materials. Alternatively, in another aspect of this invention, the pattern comprised of metal oxide may be used as a patterned hard mask for pattern transfer into an underlying semiconductor substrate using a suitable plasma, such as a fluorinated plasma.

[0192] In the inventive method, where the remaining patterned novel composition is used as a patterned hard mask after step d) rather than as a patterned high-K material, the inventive method as described above comprises an additional step e) after step d) as follows: e) The pattern composed of metal oxide is used as a patterned hard mask, i.e., an etch barrier, and etched into a semiconductor substrate using a fluorinated plasma.

[0193] In yet another embodiment of any of these methods (alternatively, methods for forming either a patterned high-K material or a patterned hard mask), the topographical features have an aspect ratio of 1:1 to 10:1. In yet another embodiment of any of these methods, the topographical features have an aspect ratio of 1 to 10 and may be selected from a range of critical dimensions (CD) of 5 nm to 100 nm, preferably 10 nm to 100 nm.

[0194] In yet another embodiment of any of the above methods, in step b), baking of the film at a temperature of 150°C to 400°C, preferably 250°C to 400°C, is carried out in two bake steps b1) and b2), where bake step b1) is carried out at 250°C to 275°C, and bake step b2) is carried out at 300°C to 400°C, preferably 350°C to 400°C. In another aspect of this embodiment, bake step b1) is carried out at 200°C to 250°C, and bake step b2) is carried out at 350°C to 400°C. In another aspect of this embodiment, bake step b1) is carried out at 250°C, and bake step b2) is carried out at 400°C. In yet another aspect, bake step b1) is carried out for 30 to 120 seconds, and bake step b2) is carried out for 60 to 120 seconds. In yet another aspect, the baking step b1) is performed for 60 to 120 seconds, and the baking step b2) is performed for 90 to 120 seconds. In yet another aspect, the baking step b1) is performed for 60 to 120 seconds. In yet another aspect, the baking step b2) is performed for 90 to 120 seconds. In yet another aspect, the baking step b1) is performed for 60 seconds. In yet another aspect, the baking step b2) is performed for 90 seconds.

[0195] In yet another aspect, the baking step b1) is performed for 1 minute and the baking step b2) is performed for 120 seconds. In yet another aspect, the baking step b1) is performed for 60 seconds. In yet another aspect, the baking step b2) is performed for 120 seconds.

[0196] Methods of using the compositions of the present invention on silicon substrates to produce patterned hard masks Another aspect of the present invention is a method for producing a patterned hard mask on an unpatterned substrate, preferably a silicon substrate, using any one of the hard mask compositions of the present invention described above, and using this pattern to produce a patterned substrate, the method comprising the following steps a3) to h3): a3) applying the composition onto a substrate to form a coating film; b3) baking the coating film at a temperature of 150 to 400°C to form a hard mask film; c3) coating a bottom anti-reflective coating on the top surface of the hard mask film; d3) coating a photoresist on top of the anti-reflective coating; e3) patterning the photoresist to form a photoresist pattern; f3) etching through the bottom antireflective coating unprotected by the photoresist pattern down to the hard mask coating using a fluorinated plasma; g3) etching with a chlorine plasma through the hard mask film unprotected by the bottom antireflective coating and the photoresist pattern down to the silicon substrate to produce a patterned hard mask film; h3) Etching into the silicon substrate in areas not protected by the patterned hardmask film using a fluorinated plasma to form topographical features in the silicon features.

[0197] In another aspect of this method, step b3) involves baking the film at a temperature of 150°C to 400°C in two bake steps b1') and b2'), where bake step b1') is performed at 150°C to 250°C and bake step b2') is performed at 300°C to 400°C. In another aspect of this method, bake step b1') is performed at 200°C to 250°C and bake step b2') is performed at 350°C to 400°C. In another aspect of this method, bake step b1') is performed at 250°C and bake step b2') is performed at 400°C. In yet another aspect, bake step b1') is performed for 30 seconds to 120 seconds and bake step b2') is performed for 60 seconds to 120 seconds.

[0198] In yet another aspect, the baking step b1') is carried out for 60 to 120 seconds, preferably 90 to 120 seconds. In yet another aspect, the baking step b2') is carried out for 90 to 120 seconds.

[0199] In yet another, the bake step b'1) is performed for 60 seconds and the bake step b2') is performed for 120 seconds.

[0200] In one embodiment, a cured film of the composition of the present invention, cured as described above, contains from about 15% to about 75% by weight of total metal oxide. In another aspect of this embodiment, the cured film contains from about 20% to about 70% by weight of metal oxide.

[0201] As previously described, patterned and cured films of the composition of the present invention for use as patterned hard masks can be produced in two ways: 1) via filling of topographical features composed of patterned photoresist or patterned organic high-carbon coatings on semiconductor substrates; or 2) via a photoresist patterning process of a cured film of the composition of the present invention on unpatterned semiconductor substrates. In either case, after etching transfer with a fluorine plasma, portions of the patterned hard mask remain after this transfer. In this example, the remaining hard mask pattern is strippable in a chemical solution.

[0202] Another aspect of the present invention is novel spin-on high carbon polymers comprising repeating units of structure (XII), where fAr is a fused aromatic ring and R 16 and R 17 are each independently hydrogen or C1-C4 alkyl. In another aspect of this embodiment, fAr is a group containing 2 to 8 fused aromatic rings. In yet another aspect, fAr is anthracene. In yet another aspect, the repeat unit has structure (XIIa). In yet another aspect, it has structure (XIIb). In yet another aspect, it has structure (XIIc). In yet another aspect, it has structure (XIIb).

[0203] [ka] Another aspect of the present invention is a novel spin-on high carbon polymer comprising repeating units selected from the group consisting of repeating units having structures (XIII), (XIIIa), (XIIIb), (XIIIc), and (XIIId), and mixtures thereof. Another aspect of this embodiment is the novel spin-on high carbon polymer comprising repeating units selected from (XIIIe), (XIIIf), (XIIIg), (XIIIh), and (XIIIi), and mixtures thereof. In another aspect of this embodiment, R 16 and R 17 is C1-C6 alkyl. In yet another embodiment, R 16 and R 17 is C1-C4 alkyl. In yet another embodiment of this aspect, R 16 and R 17 is hydrogen. In yet another embodiment, R 16 and R 17 is methyl. In yet another embodiment, R a1 , R a2 and R a3 is hydrogen.

[0204] [ka] Another aspect of the present invention is a novel spin-on high carbon polymer comprising a repeating unit having structure (XIV). In another aspect of this embodiment, it comprises a repeating unit selected from the group consisting of repeating units having structure (XIVa). In another aspect, R a1 , R a2 and R a3is hydrogen. Similarly, in these embodiments, optional repeat units can be present in which the alkynyloxy groups in these repeat units are replaced with hydroxy groups in the molar ratios described above. Additionally, in other optional repeat units, the alkynyloxy groups in these repeat units can be replaced with hydrogen, aryl, or C1-C6 alkyl groups, and such optional repeat units can be present in component b) in a proportion of up to about 20 mol % of the total; in one aspect, they are present in a proportion of up to about 10 mol %, in yet another aspect, up to 5 mol %, and in yet another aspect, up to 1 mol %.

[0205] [ka] Another aspect of the present invention is a novel spin-on high carbon polymer comprising a repeat unit having structure (XIc). In another aspect of this embodiment, the spin-on high carbon polymer comprises a repeat unit having structure (XIb). Similarly, in these embodiments of component b), optional repeat units can be present in which the alkynyloxy groups in these repeat units are replaced with hydroxy groups in the molar ratios described above. Additionally, in other optional repeat units, the alkynyloxy groups in these repeat units can be replaced with hydrogen, aryl, or C1-C6 alkyl groups, and such optional repeat units can be present in component b) in an amount of up to about 20 mol % of the total; in one aspect, they are present in an amount of up to about 10 mol %, in yet another aspect, up to 5 mol %, and in yet another aspect, up to 1 mol %.

[0206] [ka] Another aspect of the present invention is the use of the composition or spin-on high carbon polymer described above for the formation of a coating film on a substrate, preferably in the manufacture of an electronic device. [Example]

[0207] More specific embodiments of the present disclosure and experimental results supporting such embodiments will be described below. However, it should be noted that the following disclosure is for illustrative purposes only and is not intended to limit the scope of the claimed invention in any way. The term "parts" used in the following description refers to parts by mass unless otherwise specified.

[0208] Polymer molecular weights were determined using a Waters 2695 Alliance Separation Module or a Waters Dual Wave Range UV Detector, Model 2487 or equivalent, a Waters Differential Refractometer, Model 2414, detector equivalent, and a Showdex column set (one Showdex GPC KF-801 (1.5 × 10 3 ) column, two Showdex GPC KF-802 (5 × 10 3 ) column and one Showdex GPC KF-804 (4 × 10 5 The molecular weights were measured by gel permeation chromatography using an equivalent equipped with a 1000-milliliter (1000-milliliter) column. The mobile phase was UV-stabilized HPLC-grade THF, and the molecular weight standards were polystyrene standard sets supplied by American Standards Corporation and Millipore Corporation or equivalents.

[0209] AZ® ArF Thinner (also known as 70 / 30 PGMEA / PGME) was obtained from EMD Performance Materials Corporation (70 Meister Avenue, Somerville, NJ). Ti(IV), butoxide polymer (BTP), pentaerythritol ethoxylate (3 / 4 EO / OH), and other chemicals were purchased from Sigma-Aldrich Corporation (St. Louis, MO, USA) unless otherwise noted.

[0210] The refractive index (n) and extinction coefficient (k) values ​​of the metal oxide coating examples below were measured on a J.A. Woollam VASE 32 ellipsometer.

[0211] The thermogravimetric analysis used to measure the Ti wt% or other metal content was performed using a PerkinElmer Thermogravimetric Analyzer TGA7, heating from 50°C to 800°C at a heating rate of 120°C / min in an O2 atmosphere and maintaining this temperature for 60 minutes.

[0212] Elemental analyses used to determine the wt % Ti or other metal content and wt % Si content were performed by Intertek, Whitehorse, New Jersey.

[0213] The amount of said spin-on carbon polymer of component b) is usually less than 100% of the metal compound, preferably less than 50% of the metal compound.

[0214] The solvent is typically a solvent or mixture of solvents containing alcohols, esters, ketones, lactones, and diketones. Additional ingredients (<1%) such as surfactants can be added to improve the quality of the coating.

[0215] Spin-on carbon polymer synthesis Uncapped, high-carbon precursors were prepared by an acid-catalyzed condensation method involving aromatic and fused aromatic materials functionalized with phenolic moieties. The molecular weights of these precursors were adjusted by varying the molar ratio of the raw materials involved in the condensation reaction or by varying the mole percent of the acid catalyst. For example, higher molecular weights were obtained by using a lower mole percent of the acid catalyst (e.g., trifluoromethanesulfonic acid) (e.g., Polymer Synthesis Examples 2a and 3a). Alternatively, in copolymerizations of materials such as 9-fluorenone-like derivatives, increasing the molar ratio of these 9-fluorenone-like derivatives to the comonomer to approach a 1:1 molar ratio increased the molecular weight, while decreasing this ratio decreased the Mw (e.g., in Polymer Synthesis Example 1a, the molar ratio of moles of 9-fluorenone to moles of 9,9-bis(4-hydroxyphenyl)fluorene was 0.167).

[0216] Polymer Synthesis Example 1a: Polymerization of 9-fluorenone and 9,9-bis(4-hydroxyphenyl)fluorene A reaction vessel equipped with a stirrer, a Liebig condenser, a heater, a nitrogen inlet tube, and a temperature controller was prepared. 9-Fluorenone (50 g, 0.227 mol, Tokyo Chemical Industry Co., Ltd.), 9,9-bis(4-hydroxyphenyl)fluorene (583 g, 1.667 mol, Osaka Gas Chemicals Co., Ltd.), and dichloromethane (2656 g) were charged to the reaction vessel, stirred under a nitrogen atmosphere, and heated to 40 °C and maintained at this temperature. Next, trifluoromethanesulfonic acid (92 g, TCI) and 3-mercaptopropionate (5 g, TCI) dissolved in dichloromethane (200 g) were slowly added to the reaction vessel and stirred at 40 °C for 4 hours. After completion of the reaction, the reaction solution was cooled to room temperature. Sufficient water was added to the reaction solution, and excess 9,9-bis(4-hydroxyphenyl)fluorene was removed by filtration. The precipitate was washed with dichloromethane. Sufficient water was added to the dichloromethane solution to remove trifluoromethanesulfonic acid. The resulting solution was then distilled at 40°C and 10 mmHg to remove the dichloromethane and obtain the P1 precursor (468 g). Mn and Mw were measured by GPC (tetrahydrofuran). Mn was 727 Da. Mw was 991 Da. The molecular weight distribution (Mw / Mn) was 1.36. Higher molecular weights of this material could be obtained by increasing the molar ratio of 9-fluorenone to 9,9-bis(4-hydroxyphenyl)fluorene to approach 1:1.

[0217] Polymer Synthesis Example 1b: Alkynyl-capped polymer of Example 1a A reaction vessel was prepared with a stirrer, a condenser (Liebig condenser), a heater, a nitrogen inlet tube, and a temperature controller. The reaction vessel was charged with 200 g of the polymer from Polymer Synthesis Example 1a, 323 g of potassium carbonate, and 616 g of acetone, and the temperature was maintained at 56°C while stirring under a nitrogen atmosphere. 278 g of 3-bromo-1-propyne was then added to the reaction vessel, and the reaction was continued for 3 hours while stirring and maintaining the temperature at 56°C. After completion of the reaction, the reaction solution was cooled to normal room temperature. Excess potassium carbonate and its salts were removed by filtration. The precipitate was washed with acetone. The acetone solution was then distilled at 40°C and 10 mmHg to remove the acetone and obtain a dry solid. The resulting dry solid was dissolved in 820 g of ethyl acetate. Sufficient water was added to the ethyl acetate solution to remove metal impurities. The ethyl acetate solution was distilled at 40°C and 10 mmHg to remove the ethyl acetate and obtain a dry solid. This dried solid (185 g) was dissolved in acetone (185 g). Methanol (1850 g) was then added to the acetone solution, and the mixture was filtered to obtain a solid. The solid was dried at 100°C and 10 mmHg. The resulting product was P1 (76 g). Mn and Mw were measured by GPC (tetrahydrofuran). Mn was 789 Da. Mw was 1054 Da. The molecular weight distribution (Mw / Mn) was 1.34. A higher molecular weight version of this polymer was obtained by using as a starting material a polymer obtained by a modification of Polymer Synthesis Example 1a, in which the molar ratio of 9-fluorenone to 9,9-bis(4-hydroxyphenyl)fluorene was increased to approach 1:1.

[0218] Polymer Synthesis Example 2a: Polymerization of 9-anthracenemethanol, 4-divinylbenzene, ortho-phenylphenol, and 9,9-bis(4-hydroxyphenyl)fluorenone 104.1 g (0.5 mol) of 9-anthracenemethanol (MW 208.26, B&C), 42.5 g (0.25 mol) of 2-phenylphenol (MW 170.21, Aldrich), 65.1 g (0.5 mol) of divinylbenzene (MW 130.19, Aldrich), and 85.6 g (0.25 mol) of 9,9-bis(4-hydroxyphenyl)fluorene (MW 350.42, TCI) were added to a 3 L four-neck round-bottom flask equipped with a stirrer, nitrogen purge, condenser, Dean-Stark trap, and temperature controller. 700 g of diglyme and 200 g of cyclopentyl methyl ether (CPME) were added and mixed for 10 minutes. 4.5 g (1.5%) of trifluoromethanesulfonic acid was added and mixed for 10 minutes. The flask was heated to reflux at 140°C for 2 hours. The Dean-Stark trap collected water and solvent from the reaction (approximately 80 g). The reaction was stopped and allowed to cool. The reaction mixture was transferred to a 5 L separatory flask, and when the reaction mixture cooled to below 60°C, 400 mL of CPME was added and mixed for 10 minutes. The reaction mixture was extracted three times with 400 mL of deionized water. The resulting thick solution was precipitated in 8 L of hexane and mixed for 30 minutes. The precipitate was filtered, collected, and dried in a vacuum oven to recover 260 g of polymer. The recovered polymer was dissolved in THF (25 wt% solids) and precipitated in 8 L of hexane. The precipitate was filtered, washed with hexane, collected, and dried overnight in a vacuum oven to yield 213 g of polymer (71% yield). GPC Mw - 1918, Mn - 1078, Pd - 1.78. EA: [Calculated values: C: 88.90%, H: 6.09%, O: 5.00; Found values: 88.99%, H: 5.89%, O: 5.12%].

[0219] Polymer Synthesis Example 2b: Alkynyl-Capped Polymer of Example 2a A reaction vessel was prepared with a stirrer, a condenser (Liebig condenser), a heater, a nitrogen inlet tube, and a temperature controller. The alkynyl-capped polymer of Example 2a (30 g), potassium carbonate (39 g), and DMF (158 g) were charged to the reaction vessel and maintained at 100°C with stirring under a nitrogen atmosphere. 3-Bromo-1-propyne (36 g) was then added to the reaction vessel, and the reaction was continued for 4 hours at 100°C with stirring. After completion of the reaction, the reaction solution was cooled to room temperature. The solution was poured into deionized water (1500 g) and filtered. The precipitate was washed with ethyl acetate (1000 g). The ethyl acetate solution was then washed with deionized water to remove metal impurities. The ethyl acetate solution was then distilled at 60°C and 35 hPa to remove the ethyl acetate, yielding a dry solid. The solid was dried at 100°C and 10 mmHg. Mn: 1219, Mw: 2211, FT-IR shows OH peak (3600 cm -1 ) was not observed, and the H peak on the ethynyl group (3300 cm -1 ) was observed.

[0220] Polymer Synthesis Example 3a: Polymerization of 9-anthracenemethanol, 4-divinylbenzene, and ortho-phenylphenol 100.0 g of 9-anthracenemethanol (MW 208.26, B&C), 82.0 g of 2-phenylphenol (MW 170.21, Aldrich), and 63.0 g of divinylbenzene (MW 130.19, Aldrich) were added to a 3 L four-neck round-bottom flask equipped with a stirrer, nitrogen purge, condenser, Dean-Stark trap, and temperature controller. 150 g of diglyme and 55 g of cyclopentyl methyl ether (CPME) were added and mixed for 10 minutes. 2.5 g of trifluoromethanesulfonic acid was added and mixed for 10 minutes. The flask was heated to reflux at 140°C for 1 hour. Water and solvent were collected from the reaction (approximately 6.9 g) using the Dean-Stark trap. The reaction was stopped and allowed to cool. The reaction mixture was transferred to a 5 L separatory flask, and when the reaction mixture had cooled to below 60°C, 400 mL of CPME was added and mixed for 10 minutes. The reaction mixture was extracted three times with 400 mL of deionized water. The resulting thick solution was precipitated in 8 L of heptane and mixed for 30 minutes. The precipitate was filtered, collected, redissolved in THF, reprecipitated, and dried, and the same procedure was repeated two more times. The resulting solid polymer was dissolved in THF and precipitated in methanol, collected, and dried to give a white polymer (70% yield). GPC Mw: 1714, polydispersity (PD): 1.8. EA: [EA Found C: 91.16%, H: 6.18%].

[0221] Polymer Example 3b: Alkynyl-capped polymer of Example 3a A reaction vessel was prepared with a stirrer, a condenser (Liebig condenser), a heater, a nitrogen inlet tube, and a temperature controller. Polymer Example 3a (2 g), potassium carbonate (2.5 g), and DMF (8.5 g) were charged to the reaction vessel and maintained at 60°C with stirring under a nitrogen atmosphere. 3-Bromo-1-propyne (3.2 g) was then added to the reaction vessel and the reaction was continued for 3 hours at 60°C with stirring. After completion of the reaction, the reaction solution was cooled to room temperature. The solution was poured into deionized water (100 g) and filtered. The precipitate was washed with dichloromethane (50 g). The dichloromethane solution was then washed with deionized water to remove metal impurities. The dichloromethane solution was then distilled at 60°C and 35 hPa to remove the dichloromethane and obtain a dry solid. The dried solid (3 g) was then dissolved in dichloromethane (3 g) and the solution was poured into heptane (30 g). The solution was then filtered and dried at 80° C. for 12 hours. The solid (3 g) was then dissolved in THF (12 g) and the polymer solution was poured into heptane (15 g). The solution was filtered to obtain a solid. The solid was dried at 100° C. and 10 mmHg to obtain 2 g of a white polymer. Mn: 1659, Mw: 1228. FT-IR showed an OH peak (3600 cm). -1 ) was not observed, and the H peak on the ethynyl group (3300 cm -1 ) was observed.

[0222] Polymer Synthesis Example 4a: Polymerization of 14-([1,1'-biphenyl]-4-yl)-14H-dibenzo[a,j]xanthene-3,11-diol and 9,9-bis(4-hydroxyphenyl)fluorene 288.32 g of 9-fluorenone (1.6 mol), 373.2 g (0.8 mol) of 14-([1,1'-biphenyl]-4-yl)-14H-dibenzo[a,j]xanthene-3,11-diol, 380.32 g (0.8 mol) of 9,9-bis(4-hydroxyphenyl)fluorene, and 2825 g of methylene chloride were added to a 5 L four-neck round-bottom flask equipped with a stirrer, nitrogen purge, condenser, and temperature controller. The mixture was dissolved at room temperature and flushed with N2. After dissolution, 11.48 g of 3-mercaptopropionic acid (0.11 mol) and 122 g of trifluoromethanesulfonic acid were added, and the mixture was heated to 38°C under N2 and allowed to react for 8 hours. After this time, 900 g of methylene chloride was distilled off. Then, 3 L of CPME was added, and the mixture was washed with distilled water until a neutral pH was achieved. The washed CPME and dried layer were precipitated in 20 L of Isopar C. The resulting solid polymer was dried to give a white polymer (62% yield). GPC Mw: 1934, polydispersity (PD): 1.5.

[0223] Polymer Synthesis Example 4b: Alkynyl-Capped Polymer of Example 4a The material of Polymer Synthesis Example 4a was capped in the same manner as Polymer Synthesis Example 3b, using a similar molar ratio of moles of phenol-containing moieties in the polymer to moles of 3-bromo-1-propyne. The polymer was isolated in the same manner to give, after drying, approximately a 60 mole % yield of white polymer.

[0224] Polymer Synthesis Example 5a: Polymerization of 9-Fluorenone and Resorcinol A reaction vessel equipped with a stirrer, a Liebig condenser, a heater, a nitrogen inlet tube, and a temperature controller was prepared. 9-Fluorenone (150 g, Tokyo Chemical Industry Co., Ltd., hereafter referred to as TCI), resorcinol (100 g, TCI), and dichloromethane (1300 g) were charged to the reaction vessel, stirred under a nitrogen atmosphere, and heated to 40°C and maintained at this temperature. Next, trifluoromethanesulfonic acid (68 g, TCI) and 3-mercaptopropionate (4 g, TCI) dissolved in dichloromethane (200 g) were slowly added to the reaction vessel and stirred at 40°C for 4 hours. After completion of the reaction, the reaction solution was cooled to room temperature. Sufficient water was added to the reaction solution, and excess resorcinol was removed by filtration. The precipitate was washed with dichloromethane. Sufficient water was added to the dichloromethane solution to remove trifluoromethanesulfonic acid. The resulting solution was then distilled at 40°C and 10 mmHg to remove dichloromethane and obtain a dry solid. The dry solid was then dissolved in acetone (1100 g) and the solution was poured into heptane (550 g). The solution was then filtered, and the resulting solution was distilled at 50°C and 10 mmHg to remove acetone and heptane. The resulting product was the precursor (65 g). Mn and Mw were measured by GPC (tetrahydrofuran). Mn was 1364 Da. Mw was 2086 Da. The molecular weight distribution (Mw / Mn) was 1.51.

[0225] Polymer Synthesis Example 5b: Alkynyl-Capped Polymer of Example 5a A reaction vessel equipped with a stirrer, a Liebig condenser, a heater, a nitrogen inlet tube, and a temperature controller was prepared. The precursor (66 g), potassium carbonate (202 g), and DMF (303 g) were charged to the reaction vessel and maintained at 100°C with stirring under a nitrogen atmosphere. 3-Bromo-1-propyne (182 g) was then added to the reaction vessel and the reaction was continued for 3 hours at 100°C with stirring. After completion of the reaction, the reaction solution was cooled to room temperature. The solution was poured into deionized water (1500 g) and filtered. The precipitate was washed with dichloromethane (150 g). The dichloromethane solution was then washed with deionized water to remove metal impurities. The dichloromethane solution was then distilled at 60°C and 35 hPa to remove the dichloromethane and obtain a dry solid. Next, this dry solid (90 g) was dissolved in propylene glycol monomethyl ether acetate (368 g), and the solution was poured into heptane (184 g). The solution was then filtered and dried at 80°C for 12 hours. The resulting polymer weighed a total of 22 g. Mn and Mw were measured by GPC (tetrahydrofuran). Mn was 1104 Da. Mw was 1715 Da. The molecular weight distribution (Mw / Mn) was 1.55.

[0226] metal complexes Metal complex synthesis example 1 40 g of titanium(IV) butoxide polymer (Ti(IV)BTP polymer) (Sigma-Aldrich Corporation, St. Louis, MO) (0.1174 mol) was dissolved in 52 g of 70 / 30 PGMEA / PGME solvent and poured into a reaction vessel under N2. The solution was stirred, and the temperature was increased to 50 °C while 12 g (0.1330 mol) of trimethylsilanol was added dropwise under N2. The reaction mixture was maintained at 60 °C for 2 hours, after which 20 g of 1,2-cyclohexanedicarboxylic anhydride (0.1297 mol) and 20 g of 70 / 30 PGMEA / PGME were mixed with the reaction mixture, and the reaction was continued at 60 °C for approximately 1 hour. After cooling to room temperature overnight, the product was placed in an amber bottle and carefully sealed. FT-IR spectra of the product solution were obtained in cyclohexane. 970 cm -1 The resonance at 1000 nm was assigned to the Ti-O-Si stretching frequency. The total metal oxide content was measured to be 28 wt% in the film after baking at 150 °C for 60 s.

[0227] Metal complex synthesis example 2 200 g of Hf(IV) tetra-n-butoxide (0.4247 mol) was dissolved in 276 g of 70 / 30 PGMEA / PGME and poured into a reaction vessel under N2. The temperature was increased to 50°C with stirring, and trimethylsilanol (76 g, 0.8426 mol) was added dropwise to the solution with stirring under N2. The reaction was maintained at 60°C for 2 hours. Next, 127 g of 1,2-cyclohexanedicarboxylic anhydride (0.8238 mol) and 127 g of 70 / 30 PGMEA / PGME were mixed with the reaction mixture, and the reaction was continued at 60°C for approximately 1 hour. After cooling to room temperature overnight, the product was placed in an amber bottle and carefully sealed. The total Hf content measured in the film after baking at 250°C for 60 seconds was 45 wt%.

[0228] Metal complex synthesis example 3 200 g of Zr tetra-n-butoxide (80% in n-butanol) (0.4170 mol) was dissolved in 246.5 g of 70 / 30 PGMEA / PGME and poured into a reaction vessel under N2. The temperature was increased to 50°C with stirring, and 77.5 g (0.8592 mol) of trimethylsilanol was added dropwise to the solution with stirring under N2. The reaction was maintained at 60°C for 2 hours. Next, 103 g of 1,2-cyclohexanedicarboxylic anhydride (0.66814 mol) and 103 g of 70 / 30 PGMEA / PGME were mixed with the reaction mixture, and the reaction was continued at 60°C for approximately 1 hour. After cooling to room temperature overnight, the product was placed in an amber bottle and carefully sealed. An FT-IR spectrum of the product solution was obtained in cyclohexane. 1559 cm -1 and 1456 cm -1 The resonance at was assigned to the COO stretching frequency of the Zr complex. The measured total Zr content was 26.8 wt% in the film after baking at 250 °C for 60 s.

[0229] Metal Complex Synthesis Example 4 20 g of Zrn-butoxide (80% in n-butanol) (0.0417 mol) was dissolved in 27.6 g of 70 / 30 PGMEA / PGME and poured into a reaction vessel under N2. While stirring, the temperature was raised to 50°C, and 7.6 g (0.08426 mol) of trimethylsilanol was added dropwise to the solution under N2 with stirring. The reaction was maintained at 60°C for 2 hours. 9.3 g of citraconic anhydride and 9.3 g (0.08300 mol) of 70 / 30 PGMEA / PGME were then mixed with the reaction mixture, and the reaction was continued at 60°C for approximately 1 hour. After cooling to room temperature overnight, the product was placed in an amber bottle and carefully sealed. FT-IR spectra of the product solution were obtained in cyclohexane. 1565 cm -1 and 1454 cm -1 The resonance at was assigned to the COO stretching frequency of the Zr complex. The measured total Zr content was 25.4 wt% in the film after baking at 250 °C for 60 s.

[0230] Metal Complex Synthesis Example 5 40 g of Ti(IV)BTP polymer (0.1175 mol) was dissolved in 58 g of 70 / 30 PGMEA / PGME solvent and poured into a reaction vessel under N2. The temperature was increased to 50°C with stirring, and 18 g (0.1996 mol) of trimethylsilanol was added dropwise under N2. The reaction was maintained at 60°C for 2 hours. Then, 20 g of 1,2-cyclohexanedicarboxylic anhydride (0.1297 mol) and 20 g of 70 / 30 PGMEA / PGME solvent were mixed with the reaction mixture, and the reaction was continued at 60°C for approximately 1 hour. After cooling to room temperature overnight, the product was placed in an amber bottle and carefully sealed. The total metal oxide content was measured to be 32 wt% in the film after baking at 150°C for 60 seconds.

[0231] Metal Complex Synthesis Example 6 7.99 g [0.0235 mol] of Ti(IV)BTP polymer was dissolved in 14.36 g of 70 / 30 PGMEA / PGME solvent and poured into a reaction vessel under N2. The temperature was raised to 50°C with stirring, and then 7.0 g [0.0455 mol] of 1,2-cyclohexanedicarboxylic anhydride and 10.5 g of 70 / 30 PGMEA / PGME solvent were added slowly under N2. The reaction was maintained at 60°C for 2 hours. 9.8 g [0.0465 mol] of p-tolyltrimethoxysilane was then added, and the reaction was continued at 60°C for approximately 3 hours. After cooling to room temperature overnight, the product was placed in an amber bottle and carefully sealed. An FT-IR spectrum of the product solution was obtained. 1568.06 cm -1 and 970cm -1 The resonances at were assigned to the Ti-OC and Ti-O-Si stretching frequencies, respectively.

[0232] Blended Preparations The ingredients of the following examples were combined in the proportions set forth in the examples and then filtered through a 0.2 micron PTFE (polytetrafluoroethylene) filter to remove particulate matter. Blend Formulation Example 1: Blend of Polymer Example 1b, Ethanolamine, and Metal Complex Synthesis Example 1 [80:20:40] An 80:20:40 weight ratio blend formulation of Metal Complex Synthesis Example 1, triethanolamine, and Polymer Example 1b was prepared by combining 2.0571 g of a 50 wt % solution in 70 / 30 PGMEA / PGME with 0.2571 g of triethanolamine, 5.1439 g of a 10 wt % solution of Polymer Example 1b, and 2.5429 g of Polymer Example 1b. ArF-thinner solvent was added to the bottle. Therefore, the total solids content of the formulation was 18 wt % to achieve the target film thickness required for the fill test.

[0233] Blend Formulation Example 2: Blend of Polymer Example 1b and Metal Complex Synthesis Example 1 [50:50] A 50:50 weight ratio blend formulation of Metal Complex Synthesis Example 1 and Polymer Example 1b was prepared by combining 1.40 g of a 50 wt % solution of Metal Complex Synthesis Example 1 in ArF thinner, 7 g of a 10 wt % solution of Polymer Example 1b, and 1.6 g of ArF thinner. This provided a 14 wt % solids solution necessary to achieve the target film thickness required for the filling tests.

[0234] Blend Formulation Example 3: Blend of Polymer Example 2b and Metal Complex Synthesis Example 1 [50:50] A 50:50 weight ratio blend formulation of Metal Complex Synthesis Example 1 and Polymer Example 2b was prepared by combining 1.40 g of a 50 wt % solution of Metal Complex Example 1 in ArF thinner, 7 g of a 10% solution of Polymer Example 2b in ArF thinner, and 1.6 g of the ArF thinner solution, which provided a 14 wt % solids solution necessary to achieve the target film thickness required for the fill tests.

[0235] Blend Formulation Example 4: Blend of Polymer Example 2b, Ethanolamine, and Metal Complex Synthesis Example 1 [80:20:40] Samples were prepared by adding 1.8286 g of a 50 wt % solution of Metal Complex Synthesis Example 1 to 4.5714 g of a 10 wt % solution of Polymer Example 2b in ArF thinner, added to 0.2286 g of triethanolamine and 3.3714 g of ArF thinner. This provided a 14 wt % solids solution necessary to achieve the target film thickness required for the filling tests.

[0236] Blend Formulation Example 5: Blend of Polymer Example 2b and Metal Complex Synthesis Example 1 [50:50] A 50:50 weight ratio blend formulation of Metal Complex Synthesis Example 1 and Polymer Example 3b was prepared by combining 1.40 g of a 50 wt % solution of Metal Complex Example 1 in ArF thinner, 7 g of a 10% solution of Polymer Example 3b in ArF thinner, and 1.6 g of ArF thinner solution, which provided a 14 wt % solids solution necessary to achieve the target film thickness required for the fill tests.

[0237] Blend Formulation Example 6: Blend of Polymer Example 2b, Ethanolamine, and Metal Complex Synthesis Example 1 [80:20:40] Samples were prepared by adding 1.8286 g of a 50 wt % solution of Metal Complex Synthesis Example 1 to 4.5714 g of a 10 wt % solution of Polymer Example 3b in 0.2286 g of triethanolamine and 3.3714 g of ArF thinner. This provided a 14 wt % solids solution necessary to achieve the target film thickness required for the filling tests.

[0238] Blends of other metal complexes It is contemplated that compositions according to the present invention may be broadened to include the metal complexes described in Metal Complex Examples 2-6 blended with Polymer Synthesis Examples 1b, 2b, 3b, 4b, and 5b. One example of a specific blend contemplated is a blend of these other metal complexes with Polymer Synthesis Example 1b. Blends of these metal complexes with Polymer Synthesis Examples 2b, 3b, 4b, and 5b are also contemplated. A specific contemplated blend of the above blends is one containing a metal complex and polymer in a ratio of about 50:50. It is also anticipated that a ratio of about 80:20:40 of "metal complex:ethanolamine:polymer" may also be useful. Such blends can be prepared using the procedures described in Blend Formulation Examples 1-6, substituting Metal Complex Examples 2-6, respectively, for Metal Complex Example 1.

[0239] Comparative Blend Formulation Example 1: Blend of Polymer Example 3a and Metal Complex Synthesis Example 1 [50:50] Metal complex synthesis example 1 and polymer example 3a A 50:50 weight ratio blend formulation of was prepared by combining 1.40 g of a 50 wt % solution of Metal Complex Example 1 in ArF thinner, 7 g of a 10 wt % solution of Polymer Example 3a in ArF thinner, and 1.6 g of the 1.6 g ArF thinner solution. This provided a 14 wt % solids solution necessary to achieve the target film thickness required for the fill tests.

[0240] Stability results for example blends The Comparative Blend Formulation Example 1 formulation, when coated at a spin speed of 1500 rpm, initially exhibited low levels of particulate defects (approximately 0.08 def / cm) as detected by i-line on a KLA2350-IS High Resolution Imaging Inspection Tool (KLA-Tencor, Milpitas, CA). 2 The blend gave a coating film of 2.43 def / cm² (see below) and also good via filling, as determined in the same manner as described for the other blend samples below. However, after two weeks at -10°C, the 2 A defect level of 1.25 def / cm was observed after 2 weeks at 40°C. 2 Even under milder temperature aging conditions of 0°C or 25°C, particle levels were observed to be approximately 0.60 def / cm after only two months. 2 In contrast, Blend Formulation Examples 1-6 maintained their initial low particle levels in films coated in the same manner under these same aging conditions and showed no significant increase in defect counts when examined by KLA-2350-IS.

[0241] Test wafers for evaluating via filling Test wafers for evaluating via filling contained 650 nm deep vias with via sizes of 130, 140, 160, 200, and 300 nm. The via holes were patterned at various pitches, i.e., dense, semi-dense, and isolated pitches with hole:space ratios of 1:1, 1:1.4, and 1:6. The wafers were examined under a scanning electron microscope to evaluate via filling using x-section images of the vias.

[0242] Blend example filling results The via-filling capability was determined as follows. For the filling evaluation, via-filled pieces with via depths of approximately 650 nm were used. The film thickness of each material was determined using 6-inch or 8-inch silicon wafers. The target film thickness was determined based on the substrate depth. For this type of via wafer, a film thickness of 250 nm was selected to fill the vias with a slight overload film on the top surface of the via. The determined spin speed was used to perform filling on the via pieces. These wafers were then first baked in an OptiTrac at 250°C, followed by ACT12 at 400°C depending on the required bake temperature / time. The via-filled pieces were then subjected to film thickness measurement by SEM and X-SEM for imaging.

[0243] Filling results using Blend Example 1 This blend, using an 80:20:40 weight ratio blend of the metal compound component "Metal Complex Synthesis Example 1," the optional polyol component "Triethanolamine," and the high carbon polymer component "Synthesis Example 1b" (Mw=1041), provided good filling results without significant void formation. Other ratios of these components, namely, 80:20:30 and 80:20:20, were also tested. Of these ratios, the 80:20:40 blend was found to be the best, providing optimal via-filling performance.

[0244] Filling results using Blend Example 2 This blend, using a metal compound component "Metal Complex Synthesis Example 1" and a spin-on high carbon polymer component "Synthesis Example 1b" (Mw=1041) in a 50:50 ratio, provided good filling results without significant void formation. However, increasing the Mw of the spin-on high carbon polymer component by increasing the molar mass from 1041 to 1365 to 2536 while maintaining a relatively low level of void formation, did not exhibit the increase in the number of voids observed in the vias with increasing Mw, but still demonstrated significant void-filling capability. As noted above, the Mw of this type of polymer could be increased by reducing the amount of acid catalyst used.

[0245] Filling results using blend examples 3 to 6 These blends under test also demonstrated significant via-filling capabilities while maintaining stability against particle formation during aging at both high and low temperatures as described above.

[0246] Filling with blends containing other metal complexes and spin-on high carbon polymers It would be interesting to examine the filling capabilities of the above blends of spin-on high-carbon polymers, Polymer Examples 1b, 2b, 3b, 4b, and 5b, with Metal Complex Examples 2-6. These should also provide significant filling capabilities for vias and other hollow topographical features on patterned substrates. Without being bound by theory, capping the phenolic hydroxy moieties in these polymer examples may offer the same benefit against the problem of undesirable particle formation as seen in blends of Polymer Examples 1b, 2b, 3b, 4b, and 5b with Metal Complex Example 1. These excess free phenolic moieties could result in materials with too many free phenolic moieties from reaction with the metal complex. While this application is directed to the invention set forth in the claims, the disclosure of this application also includes: 1. A composition comprising the following components a), b), optionally c), and d): a) Metal compounds having the structure (I): [ka] [In the formula, M is a metal having a valence of 4; n is an integer from 1 to 20; R 1 、R 2 、R 3 , and R 4 are each independently selected from the group consisting of 1), 2), 3), and 4): 1) a first organic moiety having the structure (II):

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

change

Claims

1. A composition comprising the following components a), b), and optionally c), and d): a) A metal compound having the structure (I): 【Chemistry 1】 [In the formula, M is a metal having a valence of 4; n is an integer from 1 to 20; R 1 , R 2 , R 3 , and R 4 are each independently selected from the group consisting of 1), 2), 3), and 4): 1) a first organic moiety having the structure (II): 【Chemistry 2】 (In the formula, R 5 is C 2 ~C 10 Alkylene, C 3 ~C 12 Branched alkylene, C 5 ~C 12 Cycloalkylene, C containing a C=C double bond 2 ~C 10 Alkylene, C containing a C=C double bond 3 ~C 12 Branched alkylene and C═C double bonds 5 ~C 12 cycloalkylene; and R 6 is hydrogen or an alkyloxycarbonyl having the structure (III): 【Chemistry 3】 Here, R 7 is C 1 ~C 8 is alkyl) 2) A silicon-containing organic moiety having at least two carbons and having the structure (IV): 【Chemistry 4】 (In the formula, R 8 and R 9 are respectively, C 1 ~C 8 Alkyl, C 3 ~C 12 Branched alkyl, C 1 ~C 8 Alkyloxy, C 3 ~C 12 Branched alkyloxy, and C 6 ~C 16 aryl; R 10 is C 1 ~C 8 Alkyl, C 6 ~C 16 Selected from the group consisting of aryl, hydroxyl, and siloxane moieties having the structure (V): 【Chemistry 5】 During the ceremony, R 11 is hydrogen, C 1 ~C 8 Alkyl, hydroxyl substituted C 1 ~C 8 Alkyl, C 6 ~C 16 aryl, and a silyl moiety having the structure (IVa), where R 8a and R 9a are respectively, C 1 ~C 8 Alkyl, C 3 ~C 12 Branched alkyl, C 1 ~C 8 Alkyloxy, C 3 ~C 12 Branched alkyloxy, and C 6 ~C 16 aryl; R 10a is C 1 ~C 8 Alkyl and C 6 ~C 16 aryl; 【Chemistry 6】 R 12 and R 13 are respectively, C 1 ~C 8 Alkyl, C 3 ~C 12 Branched alkyl, C 1 ~C 8 Alkyloxy, C 3 ~C 12 Branched alkyloxy, and C 6 ~C 16 aryl; and p represents the number of repeating units in the siloxane portion having the structure (V). 3) C 2 ~C 8 Alkyl, C 2 ~C 8 Alkyl carboxyl, C 6 ~C 20 Aryl carboxyl, fluorenyl carboxyl, fluorinated C 2 ~C 8 Alkyl carboxyl, C 2 ~C 8 Alkylsulfonyl, Fluorinated C 2 ~C 8 a second organic moiety selected from the group consisting of alkylsulfonyl, alkylsulfonyl, and mixtures thereof; and 4) A mixture of these, provided that at least both the first organic moiety having structure (II) and the silicon-containing organic moiety having at least two carbons and structure (IV) are present in the metal compound. b) a spin-on high carbon polymer having a polymer backbone comprising a monocyclic aromatic hydrocarbon moiety, a fused cyclic hydrocarbon moiety or a mixture thereof, a weight percent of carbon between 81% and 94% and being at least 5% soluble in a spin-casting solvent, wherein at least one of the monocyclic aromatic hydrocarbon moieties or the fused cyclic hydrocarbon moieties present in the spin-on high carbon polymer is functionalized with at least one alkynyloxy moiety of structure (VIII); 【Chemistry 7】 [In the formula, 【Chemistry 8】 represents the point of attachment of the alkynyloxy moiety to the monocyclic aromatic hydrocarbon moiety or the fused ring cyclic hydrocarbon moiety, and R a1 is hydrogen, halogen, cyano, unsubstituted C 1 ~C 6 Alkyl; C 1 ~C 6 C substituted with at least one substituent selected from the group consisting of alkyl, halogen and cyano 1 ~C 6 Alkyl; unsubstituted C 3 ~C 20 Aromatic ring; or C 1 ~C 6 C substituted with at least one substituent selected from the group consisting of alkyl, halogen and cyano 3 ~C 20 is an aromatic ring, R a2 and R a3 are each independently hydrogen, halogen, cyano, or unsubstituted C 1 ~C 6 Alkyl; C 1 ~C 6 C substituted with at least one substituent selected from the group consisting of alkyl, halogen and cyano 1 ~C 6 Alkyl; unsubstituted C 3 ~C 20 Aromatic ring; or C 1 ~C 6 C substituted with at least one substituent selected from the group consisting of alkyl, halogen and cyano 3 ~C 20 is an aromatic ring. c) an optional component comprised of a polyol additive having structure (VI): 【Chemistry 9】 [In the formula, X is C or N; r is at least 2; q is 0 to 2; With the proviso that when X is C, the sum of q and r is 4, and when X is N, the sum of q and r is 3; R 14 is hydrogen, C 1 ~C 8 Alkyl and C 2 ~C 8 hydroxyalkyl selected from the group consisting of: If X is N, then Y is C 1 ~C 8 alkylene, or when X is C, Y is a direct valence bond, C 1 ~C 8 and a moiety having the structure (VII): 【Chemistry 10】 During the ceremony, R 15 is C 2 ~C 8 is alkylene; s is 0 to 2; and t is 1 to 2. d) spin casting solvent; provided that the spin-on high carbon polymer comprises a repeat unit having the structure (X): 【Chemistry 11】 In the formula, A is 【Chemistry 12】 and mixtures thereof; and B is, 【Chemistry 13】 is selected from the group consisting of R x1 and R x2 are independently hydrogen, a C 1 -C 6 alkyl, an aryl moiety, or an alkynyloxy moiety of structure (VIII).

2. The composition of claim 1 , wherein the spin-on high carbon polymer comprises a repeating unit having the structure (XI): 【Chemistry 14】

3. A composition comprising the following components a), b), and optionally c), and d): a) A metal compound having the structure (I): 【Chemistry 15】 [In the formula, M is a metal having a valence of 4; n is an integer from 1 to 20; R 1 , R 2 , R 3 , and R 4 are each independently selected from the group consisting of 1), 2), 3), and 4): 1) a first organic moiety having the structure (II): 【Chemistry 16】 wherein R 5 is selected from the group consisting of C 2 -C 10 alkylene, C 3 -C 12 branched alkylene, C 5 -C 12 cycloalkylene, C 2 -C 10 alkylene containing a C═C double bond, C 3 -C 12 branched alkylene containing a C═C double bond, and C 5 -C 12 cycloalkylene containing a C═C double bond; and R 6 is hydrogen or alkyloxycarbonyl having the structure (III); 【Chemistry 17】 where R 7 is C 1 -C 8 alkyl. 2) A silicon-containing organic moiety having at least two carbons and having the structure (IV): 【Chemistry 18】 (In the formula, R 8 and R 9 are each independently selected from the group consisting of C 1 -C 8 alkyl, C 3 -C 12 branched alkyl, C 1 -C 8 alkyloxy, C 3 -C 12 branched alkyloxy, and C 6 -C 16 aryl; R 10 is selected from the group consisting of C 1 -C 8 alkyl, C 6 -C 16 aryl, hydroxyl, and a siloxane moiety having the structure (V): 【Chemistry 19】 During the ceremony, R 11 is selected from the group consisting of hydrogen, C 1 -C 8 alkyl, C 1 -C 8 alkyl substituted with hydroxyl, C 6 -C 16 aryl, and a silyl moiety having the structure (IVa), where R 8a and R 9a are each independently selected from the group consisting of C 1 -C 8 alkyl, C 3 -C 12 branched alkyl, C 1 -C 8 alkyloxy, C 3 -C 12 branched alkyloxy, and C 6 -C 16 aryl; R 10a is selected from the group consisting of C 1 -C 8 alkyl and C 6 -C 16 aryl; 【Chemistry 20】 R 12 and R 13 are each independently selected from the group consisting of C 1 -C 8 alkyl, C 3 -C 12 branched alkyl, C 1 -C 8 alkyloxy, C 3 -C 12 branched alkyloxy, and C 6 -C 16 aryl; and p represents the number of repeating units in the siloxane portion having the structure (V). 3) a second organic moiety selected from the group consisting of C2-C8 alkyl, C2-C8 alkyl carboxyl, C6-C20 aryl carboxyl, fluorenyl carboxyl, fluorinated C2-C8 alkyl carboxyl, C2-C8 alkyl sulfonyl, fluorinated C2-C8 alkyl sulfonyl, and mixtures thereof; and 4) A mixture of these, provided that at least both the first organic moiety having structure (II) and the silicon-containing organic moiety having at least two carbons and structure (IV) are present in the metal compound. b) a spin-on high carbon polymer having a polymer backbone comprising a monocyclic aromatic hydrocarbon moiety, a fused cyclic hydrocarbon moiety or a mixture thereof, a weight percent of carbon between 81% and 94% and being at least 5% soluble in a spin-casting solvent, wherein at least one of the monocyclic aromatic hydrocarbon moieties or the fused cyclic hydrocarbon moieties present in the spin-on high carbon polymer is functionalized with at least one alkynyloxy moiety of structure (VIII); 【Chemistry 21】 [In the formula, 【Chemistry 22】 represents the point of attachment of said alkynyloxy moiety to said monocyclic aromatic hydrocarbon moiety or said fused ring cyclic hydrocarbon moiety, and R a1 is hydrogen, halogen, cyano, unsubstituted C 1 -C 6 alkyl; C 1 -C 6 alkyl substituted with at least one substituent selected from the group consisting of C 1 -C 6 alkyl, halogen, and cyano; an unsubstituted C 3 -C 20 aromatic ring; or a C 3 -C 20 aromatic ring substituted with at least one substituent selected from the group consisting of C 1 -C 6 alkyl, halogen, and cyano; R a2 and R a3 are each independently hydrogen, halogen, cyano, unsubstituted C 1 -C 6 alkyl; C 1 -C 6 alkyl substituted with at least one substituent selected from the group consisting of C 1 -C 6 alkyl, halogen, and cyano; an unsubstituted C 3 -C 20 aromatic ring; or a C 3 -C 20 aromatic ring substituted with at least one substituent selected from the group consisting of C 1 -C 6 alkyl, halogen, and cyano. c) an optional component comprised of a polyol additive having structure (VI): 【Chemistry 23】 [In the formula, X is C or N; r is at least 2; q is 0 to 2; With the proviso that when X is C, the sum of q and r is 4, and when X is N, the sum of q and r is 3; R 14 is selected from the group consisting of hydrogen, C 1 -C 8 alkyl, and C 2 -C 8 hydroxyalkyl; When X is N, Y is a C 1 -C 8 alkylene; or when X is C, Y is selected from the group consisting of a direct valence bond, a C 1 -C 8 alkylene, and a moiety having the structure (VII): 【Chemistry 24】 During the ceremony, R 15 is C 2 -C 8 alkylene; s is 0 to 2; and t is 1 to 2. d) spin casting solvent; provided that the spin-on high carbon polymer comprises repeat units selected from the group consisting of repeat units having structures (XIII), (XIIIa), (XIIIb), (XIIIc) and (XIIId), and mixtures thereof: 【Chemistry 25】 In the above formula, fAr is a fused aromatic ring; R 16 and R 17 are each independently hydrogen or C 1 ~C 4 It is an alkyl.

4. 4. The composition of claim 3, wherein the spin-on high carbon polymer comprises repeating units selected from the group consisting of repeating units having structures (XIIIe), (XIIIf), (XIIIg), (XIIIh) and (XIIIi), and mixtures thereof. 【Chemistry 26】 (In the above formula, R 16 and R 17 are each independently hydrogen or C 1 ~C 4 It is alkyl.

5. The composition of claim 1 , wherein the spin-on high carbon polymer comprises a repeating unit having the structure (XIV). 【Chemical 27】

6. 6. The composition according to claim 1, wherein M is selected from the group consisting of Zr, Ta, Hf, Ti, Sn, Si, Pb, Nb, Mo, Ge and W.

7. The composition according to any one of claims 1 to 6, wherein component a) is a mixture of two or more different metal compounds having the structure (I).

8. 8. The composition of claim 1, comprising 20% ​​to 98% by weight of component a), 1% to 50% by weight of component b), and 1% to 30% by weight of component c), when component c) is present, or 20% to 98% by weight of component a) and 1% to 60% by weight of component b), when component c) is not present, each based on the total weight of the solid components, and the sum of these solid components is 100% by weight in the absence of any additional solid components.

9. The composition of any one of claims 1 to 5, wherein in said spin-on high carbon polymer, the molar ratio of free phenol to phenols capped with alkynyl moieties forming the alkyloxy moieties of structure (VIII) is less than or equal to 1.

10. 1. A method of manufacturing an electronic device, comprising: a) applying the composition according to any one of claims 1 to 9 onto a substrate to form a coating film; and b) heating the coating film at a temperature between 150° C. and 400° C. for a time period between 30 seconds and 240 seconds to form a cured coating film; The method comprising:

11. A spin-on high carbon polymer comprising repeating units selected from the group consisting of repeating units having structures (XIII), (XIIIa), (XIIIb), (XIIIc) and (XIIId) and mixtures thereof. 【Chemistry 28】 (wherein fAr is a fused aromatic ring, and Ra is 1 , Ra 2 , Ra 3 , R 16 and R 17 are each independently hydrogen and C 1 ~C 4 is selected from the group consisting of alkyl,

12. 12. The spin-on high carbon polymer of claim 11 comprising repeating units selected from the group consisting of repeating units having structures (XIIIe), (XIIIf), (XIIIg), (XIIIh) and (XIIIi) and mixtures thereof. 【Chemical 29】 (wherein fAr is a fused aromatic ring, and Ra is 1 , Ra 2 , Ra 3 , R 16 and R 17 are each independently hydrogen and C 1 ~C 4 is selected from the group consisting of alkyl,

13. A spin-on high carbon polymer comprising repeating units having structure (XIV): 【Chemistry 30】 (In the above formula, R a1 is hydrogen, halogen, cyano, unsubstituted C 1 ~C 6 Alkyl; C 1 ~C 6 C substituted with at least one substituent selected from the group consisting of alkyl, halogen and cyano 1 ~C 6 Alkyl; unsubstituted C 3 ~C 20 aromatic ring; Or C 1 ~C 6 C substituted with at least one substituent selected from the group consisting of alkyl, halogen and cyano 3 ~C 20 is an aromatic ring, R a2 and R a3 are each independently hydrogen, halogen, cyano, or unsubstituted C 1 ~C 6 Alkyl; C 1 ~C 6 C substituted with at least one substituent selected from the group consisting of alkyl, halogen and cyano 1 ~C 6 Alkyl; unsubstituted C 3 ~C 20 Aromatic ring; or C 1 ~C 6 C substituted with at least one substituent selected from the group consisting of alkyl, halogen and cyano 3 ~C 20 It is an aromatic ring.

14. R a1 , R a2 and R a3 The spin-on high carbon polymer of claim 13 , wherein is hydrogen.

15. 15. The spin-on high carbon polymer of any one of claims 11 to 14, wherein the molar ratio of free phenol to phenols capped with alkynyl moieties forming the alkyloxy moieties of structure (VIII) in the spin-on high carbon polymer is 1 or less.

Citation Information

Patent Citations

  • Anti-reflective coating composition and method thereof

    JP2014515121A

  • Composition for forming resist underlay film, resist underlay film, and method for manufacturing patterned substrate

    JP2016167047A

  • Method for forming resist underlay film and pattern forming method

    JP2016206676A

  • A stable metal compound as a hard mask and a filling material, its composition, and its method of use

    JP2016537478A

  • Material for resist underlay film, pattern forming method, and compound

    JP2017021337A